Environmental chemistry for the future: challenges, applications, and new AI-enabled pathways - Bo Weng; Minghui Zheng; Lijun Wu; Wei Chen; Cheng Gu; Liang Mao; Hui Li; Chiheng Chu; Qian Sui; Wei Zhang; Wei Shi; Qiancheng Xia; et al. (ENGINEERING Environment, 2026)

Ferrous iron-induced secondary mineral formation regulates organic carbon bioavailability and methane recovery from iron-enhanced primary sludge - Feifei Chu; Fangmei Cheng; Xiaomeng Zhang; Liyan Wei; Xinhou Zhang; Yun Chen; Lei Zhao; Fei Yang; Nan Shen (Bioresource Technology, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Iron-bound organic carbon formation governs the dual role of iron in anaerobic digestion of waste activated sludge: A stage-specific dosing strategy for enhanced methane recovery - Feifei Chu; Zhaofu Liu; Fangmei Cheng; Xiaomeng Zhang; Liyan Wei; Xinhou Zhang; Yun Chen; Lei Zhao; Fei Yang; Nan Shen (Environmental Research, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

A low-cost solar disinfection platform: hydrogel-encapsulated benzyl frameworks for continuous in situ H2O2-driven water treatment - Wenjuan Zhang; Lizheng Chen; Xiaojuan Zhao; Shiling Zhang; Chongling Cheng; Juan Du; Kaikai Ba; Bo Wang; Tengfeng Xie; Xuefeng Chu; Gang Liu; Dayang Wang (Water Research, 2026)

Nano-island Cu–Cu2O heterojunctions: Synergistic electroreduction of bromate at mixed-valence perimeters - Yu Chu; Junjie Li; Huihuan Lin; Binyu Ma; Zhipeng Luo; Yue Cheng; Xin Yu; Huabin Zeng (Journal of Water Process Engineering, 2026)

Rainfall event timing and thresholds govern reverse sap flow in desert shrubs - Zixuan Yuan; Yiben Cheng; Zhiming Xin; Yuxuan Liu; Tao Yu; Jingwen Li; Lixia Chu (Journal of Hydrology, 2026)

Effects of long-term room temperature storage on phenolic acids and furfurals in honey - Fanhua Wu; Xinyu Wang; Jinkui Wu; Dianli Yang; Chu Li; Ying Zhang; Ni Cheng; Haoan Zhao; Wei Cao (Food Chemistry, 2026)

SNX8 interacts with THOC7 to negatively regulate IFN 1 response via the TBK1-IRF3 signaling axis in teleost fish - Miao-miao Li; Chu-xin Wu; Ji-huan Hu; Ting-ting Yu; Ze-yin Jiang; Hong-ying Zhang; Xun-hang Li; Cheng-yu Hu (Fish & Shellfish Immunology, 2026)

Strigolactones constrain rice drought acclimation by suppressing ROS scavenging through the D53–OsWRKY31–ZFP36 module - Qianqian Li; Yi Wang; Jijun Yan; Liquan Kou; Hao Zhang; Jinhua Yang; Qingliang Hu; Yanshuo Guo; Xinwei Ban; Nan Luo; Peiyong Xin; Yanhui Jing; et al. (Molecular Plant, 2026)

The protective effect and mechanism of Piezo1 inhibition on blood-brain barrier injury after focal cerebral ischemia-reperfusion in rats - Chu-hua Gu; Wen-qi Song; Jia-yi Gan; Kuan Zheng; Xiao-hui Ding; Wei-cheng Lu; Hui Xie (Neurophysiology, 2026)

Podocarpusflavone A inhibits multiple myeloma cells by targeting the PI3K/AKT pathway to mediate c-Myc downregulation and activate the intrinsic apoptosis pathway - Jian Gao; Guanghui Cheng; Haimei Jiang; Jiawen Chu; Mengyuan Zhang (Toxicon, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Cyanobacteria relative biomass modulates the contrasting effects of species richness and evenness on phytoplankton resource use efficiency in a mesocosm experiment - Yafang Qin; Chaoyue Cheng; Shangsheng Sun; Ruyi Li; Misha Zhong; Yuwei Wang; Yihan Wang; Zengliang Jian; Chaokun Wang; Yulian Chu; Jianfeng Chen; Haojie Su (Science of The Total Environment, 2026)

Underappreciated role of polluted storm sewer discharge in the accumulation of antibiotic resistance genes in downstream sediments - Yu Zhang; Zuxin Xu; Wenhai Chu; Huan He; Liping Ma; Jingyi Zhang; Cheng Ye (Journal of Hazardous Materials, 2026)

Development of functionalized gelatin: Recent advances, challenges and prospects - Cheng Tang; Kezhou Cai; Xing Liu; Mengya Li; Zhijie Bao; Huanhuan Cai; Jiyang Chu; Yong Xie; Hui Zhou; Baocai Xu (Food Hydrocolloids, 2026)

Screening of immune adjuvants for an attenuated live vaccine derived from the Aeromonas veronii TH0426 strain with a hisJ gene deletion and evaluation of its immune protection in crucian carp - Qixing Huang; Ruitong Li; Shuoyu Wang; Ruiqi Liang; Peiqi Lu; Bingmei Du; Yan Cheng; Xiaochen Ren; Jinhong Li; Xu Dong; Jiaojiao Yang; Luyao Chu; et al. (Fish & Shellfish Immunology, 2026)

Cosolvent-driven exciton delocalization and dual dissociation pathways enable high-efficiency inverted all-polymer solar cells - Jia-Fu Chang; Hui Chan Ahn; Sunil V. Barma; Cheng-Yu Yeh; Yu-Cheng Tseng; Hyun Min Kwon; Hyerin Jeon; Hsu-Tzu Cheng; Bumjoon J. Kim; Sae Byeok Jo; Chu-Chen Chueh (Chemical Engineering Journal, 2026)

Double-exchange-enhanced La1-xMnO3-δ amperometric sensor with superior sensitivity for high-temperature humidity detection - Weijie Shen; Chu Cheng; Jiajun Mao; Jiawen Jian; Jie Zou (Chemical Engineering Journal, 2026)

Hormesis induced by lithium exposures influenced the effects of maternal age at reproduction on offspring quality of Brachionus calyciflorus: A multigenerational study - Fan Gao; Ziyang Zhang; Sen Feng; Tianyi Du; Meng Li; Lingyun Zhu; Bin Chu; Zhizhong Li; Xinfeng Cheng; Xianling Xiang (Aquatic Toxicology, 2026)

Assessing the Potential of a Formalin‐Killed Cells (FKC) Vaccine Against Edwardsiella anguillarum in Milkfish ( Chanos chanos ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum causes Edwardsiellosis in fish, resulting in severe internal organ lesions and substantial economic losses in aquaculture. The limited efficacy of antibiotics in treating this disease, coupled with concerns regarding resistance and side effects, has driven interest in exploring fish vaccines. Various vaccine candidates derived from E. anguillarum, including inactivated cells and protein subunits, have shown potential. Here, we developed a vaccine against E. anguillarum in milkfish, and its efficacy was evaluated through vaccination challenge trials using milkfish as the target species. The formalin‐killed vaccine (FKC) in combination with an adjuvant exhibited superior efficacy, achieving a relative percent survival (RPS) of 83.4%. Furthermore, the agglutination titers indicated a robust immune response in the FKC + Adjuvant group, suggesting a potent and sustained antibody response. Additionally, serum lysozyme activity was significantly higher in vaccinated fish than in controls. Immune‐related gene expression analysis in spleen and head kidney revealed that IL‐1β peaked at 14 days post‐vaccination, indicating early pro‐inflammatory response, while MHC‐II showed progressive elevation, suggesting sustained antigen presentation and humoral immunity. Overall, this study underscores the effectiveness of the FKC + Adjuvant combination in enhancing immune response and protecting against bacterial pathogens in aquaculture, presenting a promising strategy for disease control.

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Multi-omics Analysis Reveals the Prognostic and Therapeutic Value of TGF-β Signaling-related Genes in Idiopathic Pulmonary Fibrosis - Chenkun Fu; Xiaoting Jing; Menglin Zhang; Yiju Cheng; Wenting Yang; Xiao Wu; Xiaojuan Chu; Xiaofeng Lu (Biochemical Genetics, 2026)

Guaiane-type sesquiterpenoids with acetylcholinesterase inhibitory activities from the roots of Stellera chamaejasme - Cheng-Yu Chu; Xuan Liu; Si-Hui Mi; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Dynamic Optimization of Powder Factor in Extreme-cold Region Bench Blasting Considering Temperature Effects on Single-hole Blasting - Xin Cai; Chu Wang; Zilong Zhou; Ruishan Cheng; Jingyao Gao; Bo Liu (Rock Mechanics and Rock Engineering, 2026)

Rhodamine B degradation through sulfite activation by Vernadite: Kinetics characteristics and reaction mechanism - Wenteng Chu; Runshen Feng; Cheng Wang; Yanting Pan; Hong Su; Feng Jiang; Xiaoming Wang; Hui Yin; Xionghan Feng (Applied Geochemistry, 2026)

Influence of Fe doping on the surface hydration and dewatering behavior of kaolinite: Molecular dynamics simulations and experiments - Jun Chen; Huanhuan Shang; Xinxia Chu; Yali Cheng; Chunyun Zhu; Fanfei Min (Applied Clay Science, 2026)

n ‐Alkane Gradients Reshape Soil Microbial Networks and Functions at Petroleum Refinery Sites - Youru Zhang; Shixuan Cui; Yu Zhang; Jizhuang Chu; Kaiyue Liu; Xinjie Shan; Na Wang; Shudi Yao; Qiang Kong; Cheng Dong; Huanxin Zhang (Environmental Microbiology, 2026)
Petroleum refining activities exert substantial contamination pressure on soil ecosystems, yet the corresponding microbial response mechanisms remain insufficiently understood. This study integrates source apportionment, high‐throughput sequencing and co‐occurrence network analysis to elucidate microbial adaptations along a petroleum exposure gradient. Source analysis confirmed that all soils were predominantly influenced by petroleum‐derived inputs, with hydrocarbon concentrations increasing significantly across gradients. Under contamination levels of 422.35–621.21 mg/kg, petroleum pollution not only reduced soil total organic carbon (TOC) but also induced coupled C–N interactions and altered soil physicochemical properties, resulting in complex environmental effects. The soil quality index (SQI) exhibited a nonlinear trend, first decreasing and then increasing, with moderate overall levels (0.40–0.45). Functional diversity analyses indicated functional convergence rather than loss under contamination stress. At the metabolic level, low exposure primarily stimulated naphthalene degradation and detoxification pathways, whereas high exposure shifted microbial functions towards oxidative stress resistance and membrane structural remodelling. Meanwhile, microbial networks transitioned from densely connected but disturbance‐sensitive structures at low exposure to simplified yet more stable and robust configurations at high exposure. These findings provide mechanistic insights into microbial adaptation in petroleum‐contaminated soils and offer theoretical support for bioremediation strategies.

Pdk2 regulates skeletal muscle growth in largemouth bass (Micropterus salmoides) via modulation of glucose and lipid metabolism - Xin Zhu; Wei Zeng; Lintao Nie; Yangyang Meng; Jia Cheng; Yaxiong Pan; Wuying Chu (Aquaculture, 2026)

Heterocyclic PAH pollution risks in stormwater overflows: Mechanistic elucidation of sediments as the key contributor - Tianyi Dong; Cheng Ye; Feiyang Ao; Yao Qu; Feifei Wang; Jan Hofman; Zuxin Xu; Wenhai Chu (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects of polymer type and aging on enrichment of antibiotic resistance genes and pathogens in biofilm on microplastics in biological wastewater treatment - Cheng Qiu; Lei Zheng; Hua Wang; Yixuan Chu; Qun Wang; Yongmin Chen; Yali Song; Chengran Fang (Journal of Environmental Management, 2026)

Fine-scale post-fire forest recovery patterns and compound drivers in Taiwan’s high-mountain national parks - Chu-Chia Kuo; Yu-Ling Liu; Cheng-Tao Lin (Forest Ecology and Management, 2026)

Genomic insights and vaccine evaluation of a virulent MLST ST234 Bacillus cereus infecting Asian sea bass (Lates calcarifer) - Li-Wu Cheng; Qiong-Yi Huang; Nopadon Pirarat; Abisheik Rajandran; Sayuj Poudyal; Pei-Chi Wang; Shih-Chu Chen (Fish & Shellfish Immunology, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Evaluating in vitro bioaccessible fractions of rare earth elements in soils by using a simplified bioaccessibility extraction test - Chih-Cheng Chang; Ling-Chu Chien; Hsing-Cheng Hsi; Zeng-Yei Hseu (Environmental Geochemistry and Health, 2026)

Influence of greening forms and building wall heating conditions on traffic pollutant dispersion inside canyons - Qianfeng Liang; Cheng Yao; Dingyue Chu; Wencheng Liu; Rong Ji; Yuandong Huang; Yang Luo (Environmental Fluid Mechanics, 2026)

An interpretable and adaptive tunnel water inflow prediction method using data augmentation and AHP-Enhanced OP-LightGBM - Jingqi Cui; Shunchuan Wu; Haiyong Cheng; Xiaowei Hou; Jiaxin Wang; Weihua Liu; Chaoqun Chu (Tunnelling and Underground Space Technology, 2026)

Divergent composite contamination of pesticides on conventional and biodegradable agricultural microplastics and their contrasting toxic effects - Xiaoyu Zhang; Jieyun Cheng; Yu Zhang; Yongzheng Qiu; Yanjie Liu; Jing Wu; Jialing Chu; Ziyan Xin; Chenyue Zou; Yue Wang (Journal of Hazardous Materials, 2026)

Liquid mulching film mitigates cationic heavy metals migration via enhancing soil organic matter and cation exchange capacity - Lijuan Cha; Zhiyun Zhang; Ruiyao Shi; Fangfang Li; Gang Chu; Lincai Peng; Jing Zhao; Jing Li; Minghao Cheng; Min Wu (Journal of Environmental Sciences, 2026)

Simultaneous removal of fluoride and disinfection by-product precursors through Zr salt enhanced coagulation - Zhanghan Li; Pin Wang; Cheng Ye; Jiacheng Luo; Yayun Zhang; Wenhai Chu (Journal of Environmental Sciences, 2026)

Subchronic, low-frequency polystyrene microplastic or nanoplastic exposure elicits molecular perturbations but minimal clinical phenotypes in the mouse gut-brain axis - Sheng-Han Lee; Han Chang; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Environmental Pollution, 2026)

Scalable biomimetic high-entropy alloys/C-O composite coatings with enhanced photothermal and antibacterial performance - Bang An; Liang Wang; Chao Sun; Dongfang Chen; Wen Xu; Yong Zhang; Kun Qian; Qiangsheng Dong; Chenglin Chu; Feng Xue; Cheng Wang; Jing Bai (Chemical Engineering Journal, 2026)

Trio-active bone scaffold with multivalent ion doping establishes an osteo–angio–immune bone regenerative axis - Jiren Yan; Xiang Li; Teng Ye; Weinan Cheng; Yaping Li; Gen Wen; Fei Zhang; Linyang Chu (Chemical Engineering Journal, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Fungal diversity drives soil health and agricultural sustainability in black soils - Teng Yang; Xu Liu; Leho Tedersoo; Xiyuan Xu; Guifeng Gao; Kunkun Fan; Luyao Song; Dan Zhao; Yuying Ma; Li Nie; Di Wu; Jingjing Liu; et al. (Science Bulletin, 2026)

Transcriptome profiling of AP2/ERF family members and functional characterization of CaAP2/ERF99 in pepper defense against Phytophthora capsici - Jie Wang; Muhammad Azeem; Yawei Li; Beibei Gong; Xueqi Li; Li Liu; Guangqiang Wu; Moli Chu; Wei Cheng (Plant Science, 2026)

Removal of hexavalent chromium from water using sulfidated nanoscale zero-valent iron: Regeneration and freeze–thaw stability, mechanism, and plant ecotoxicity - Wei Yuzhen; Cheng Aobo; Liu Bei; Ma Jushan; Muhammad Hamdan Rashid; Yu Jialu; Fasih Ullah Haider; Ma Shengyuan; Zhang Qinhu; Chu Run (Journal of Water Process Engineering, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Identifying active nitrate-assimilating bacteria that alleviate secondary salinization in facility soil driven by carbon source availability - Qian Wang; Ran Liu; Cheng Chu; Yunbin Jiang; Huan Deng; Xinqi Huang; Cheng Han; Wenhui Zhong (Journal of Cleaner Production, 2026)

PWACG: Partial wave analysis code generator supporting Newton-conjugate gradient method - Xiang Dong; Yu-Chang Sun; Chu-Cheng Pan; Ao-Yan Cheng; Ao-Bo Wang; Hao Cai; Kai Zhu (Computer Physics Communications, 2026)

La-site deficient La0.7Sr0.2FeO3 electrode: Improving sensitivity and alleviating poisoning of mixed-potential SO2 sensor - Xiaoli Wang; Chu Cheng; Feng Qiu; Weijie Shen; Xiang Zhu; Jing Song; Jiawen Jian; Jie Zou (Chemical Engineering Journal, 2026)

Ecological roles of lactic acid bacteria biodiversity and cross-feeding in shaping the flavor landscape of traditional Huangjiu fermentation - Chao-Jie Zhu; Yi-Ling Zhong; Yong-Zhu Zhang; Zhi-Chu Shan; Hong-Yan Qu; Fei Cheng; Wei Feng; Peng Wang; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Bioresource Technology, 2026)

Progress and challenges in studies of earthquake rupture initiation and arrest - Sidao Ni; Yigang Xu; Chunhe Yang; Risheng Chu; Huajian Yao; Huiping Zhang; Yong Ni; Huihong Cheng; Yupeng Yao (Science China Earth Sciences, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

Correction: Dynamic Optimization of Powder Factor in Extreme-cold Region Bench Blasting Considering Temperature Effects on Single-hole Blasting - Xin Cai; Chu Wang; Zilong Zhou; Ruishan Cheng; Jingyao Gao; Bo Liu (Rock Mechanics and Rock Engineering, 2026)

Tuning Ni–O orbital interactions to steer oxygen activation for enhanced hydrogen peroxide photosynthesis - Chao Xing; Yunjie Zou; Longjie Liu; Dongdong Chu; Dayu Sun; Qi Cheng; Wenhai Chu; Lan Ling (Science Bulletin, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

A histone methylation reader suppresses both disease resistance and tillering by facilitating H3K9me1-mediated gene silencing in rice - Fengfeng Fan; Manman Liu; Huanran Yuan; Nannan Li; Mingxing Cheng; Xiong Luo; Yu Guo; Ayaz Ahmad; Meng Cai; Fengfeng Si; Zihan Yang; Man Wang; et al. (Molecular Plant, 2026)

Rainfall-driven shifts in disinfection byproduct precursors in eutrophic lakes: From algal to terrestrial sources - Fangyuan Jiang; Jiaqi Ran; Feifei Wang; Yao Qu; Kaidi Lai; Ruixin Qu; Wenyuan Yang; Cheng Ye; Wenhai Chu (Journal of Hazardous Materials, 2026)

Experimental study on methanol steam reforming for hydrogen production based on exsolution of Cu metallic nanoparticles - Xiangguo Zhang; Yushi He; Nien-Chu Lai; Chunhuan Luo; Changchang Yang; Cheng Bao (Fuel, 2026)

Optimizing wheat yields from smallholdings: Crop density-dependent benefits of wide strip sowing under varying resource availability - Jing-Wei Fan; Peiyin Jia; Shi-Cheng Li; Chu-Yi Sun; Jairo A. Palta; Shuang-Yi Kang; Xiao-Yu Lv; Li Hou; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

In-situ sulfur isotope and microscopic analyses reveal multiple pyrite genesis mechanisms in the early Ediacaran Doushantuo Formation, South China - Shiqi Cheng; Lianjun Feng; Guoqiang Tang; Yan Liu; Hao Qiu; Qiuli Li; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Whole‐Genome Single Nucleotide Polymorphism Analysis and High‐Resolution Melting ( HRM ) Differentiation of Edwardsiella anguillarum and Edwardsiella piscicida - Atiek Rahmawaty; Li Wu Cheng; Jue‐Liang Hsu; Shun Maekawa; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
This study aimed to develop a method to differentiate between two closely related bacterial species within the genus Edwardsiella , namely Edwardsiella anguillarum and Edwardsiella piscicida , which cause Edwardsiellosis in fish aquaculture. Whole‐genome single nucleotide polymorphism (SNP) analysis was conducted to assess the genetic relationships among E. piscicida , E. anguillarum and Edwardsiella ictaluri . SNP distance matrices and phylogenetic trees demonstrated that isolates within each species clustered together, confirming genetic SNP distinctiveness. SNP annotation and distance comparisons identified key genes— artI , dnaK , hlyB , ubiB , hutW , ydgD , MCP and fliC —that exhibited significant divergence. We designed specific primers targeting SNPs in these genes and used these primers for real‐time PCR and High‐Resolution Melting (HRM) analysis. HRM analysis using designed primer pairs revealed distinct melting temperature ( Tm ) peaks for E. anguillarum and E. piscicida . HRM analysis of 37 isolates that were previously identified as E. tarda based on phenotypic characteristics identified them as either E. anguillarum (35) or E. piscicida (2). These results showed that hlyB was the most reliable target gene for distinguishing between E. anguillarum and E. piscicida . The HRM technique is a fast, cost‐effective method for differentiating these closely related bacterial species and provides insights into the genetic variation among different species of Edwardsiella and host‐specific strains.

Storm-driven overflow disinfection highlights toxicity risk of chlorophenylacetonitriles: Unveiling indole in sewer sediments as a key precursor - Tianyi Dong; Cheng Ye; Wenyuan Yang; Yayun Zhang; Feifei Wang; Zuxin Xu; Zoran Kapelan; Wenhai Chu (Water Research, 2026)

Interfacial engineering of hematite trigger periodate activation reaction for sustainable sulfisoxazole removal: Mechanism insight and environmental significance enhancement - Zheng-Tao Dong; Long Sui; Ya-Ya Yang; Hai Guo; Qian Wu; Yuan Tian; Lei Ma; Chu-Jia Jin; Ming Yan; Cheng-Gang Niu (Journal of Hazardous Materials, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Impact of PFOS on maternal and placental lipid metabolism and decreased placental vascularization in a murine model - Zheyu Cheng; Hin Ting Wan; Wing Yee Chan; Thomas Ka Yam Lam; Chris Kong Chu Wong (Journal of Hazardous Materials, 2026)

Pullout behavior investigation of connecting rebars in mortise-tenon joints for precast concrete shear walls - Zhijuan Sun; Xiaowei Cheng; Lei Liu; Qi Wang; Jiliang Liu; Mingjin Chu; Xiuli Du (Engineering Structures, 2026)

Chitosan‑selenium nanoparticles alleviate fluoride-induced hippocampal neurotoxicity by targeting the DUSP5-ERK-CREB-BDNF signaling axis - Haojie Li; Fangyu Yan; Cheng Huang; Weijiang Chu; Rongze Wang; Tianyu Wang; Hui Zhao; Yuanyuan Li; Jiarong Yang; Zijun Hao; Yufeng Gao; Jie Ren; et al. (Chemical Engineering Journal, 2026)

Water table-driven divergent patterns and drivers of particulate and mineral-associated organic carbon in alpine peatlands - Han Zheng; Mengjie Liu; Houkun Chu; Paul P.J. Gaffney; Junxiao Pan; Quan-Cheng Wang; Yang Li; Dashuan Tian; Ruiyang Zhang; Ronglei Zhou; Ning Liu; Fei Wu; et al. (CATENA, 2026)

Large eddy simulation and laboratory experiments of ice melting in steady currents and surface waves - Chia-Ren Chu; Cheng-Han Yu; Fang-Yu Fan; Hwa Chien; Tso-Ren Wu (Cold Regions Science and Technology, 2026)

Lactiplantibacillus plantarum SG053 and SG066 Enhance Nutritional Value of Soy Protein via Improved Essential Amino Acid Bioavailability - David Agus Setiawan Wibisono; Chiou-Yeong Saw; Der-Kai Lau; Wei-Jen Chen; Hui-Fang Chu; Cheng-Yen Liu; Chi-Fai Chau (Probiotics and Antimicrobial Proteins, 2026)

TigerNet: individual identification of Stripe patterns in Amur Tigers like human fingerprint - Chunmei Shi; Hao Fan; Nathan James Roberts; Wannian Cheng; Chenbing Chu; Yao Ning; Guangshun Jiang (Mammal Research, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Regulated enzyme distribution for enhanced wearable sweat glucose monitoring - Yao Chu; Yangyang Chen; Zhen Gu; Xinyi Liu; Tao Cheng; Yichuan Shen; Jian Lv; Yiping Wu; Nan Chen; Haifeng Yang; Wanxin Tang (Analytica Chimica Acta, 2026)

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Identification, sources and accumulation behavior of priority odorants discharged to surface water from stormwater systems with illicit connections - Cheng Ye; Fangyuan Jiang; Feifei Wang; Zoran Kapelan; Zuxin Xu; Michael R. Templeton; Wenhai Chu (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Drought-induced shifts in rhizosphere microbiota correlate with reprogramming of floral volatiles in Chrysanthemum morifolium ‘Gongju’ - Zhuannan Chu; Mingzhe Cheng; Yuning Sun; Weiwen Li; Dongmei Yin (Rhizosphere, 2025)

Integrative control of plant sex determination: Genes, hormones, and environment - Wei Li; Yiming Wang; Ronghua Qian; Yi Yao; Xiang Xue; Jie Chen; Jun Chu; Caihong Zhu; Suke Xu; Cheng Qi Yi; Xu Yang (Plant Science, 2025)

Conventional microplastics pose higher short-term risks to crop growth than biodegradable alternatives: Evidences from a two-year field trial - Yan Liu; Juncong Chu; Lang Cheng; Zhengjun Yan; Yue Wang; Junyong Ge; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Cleaner Production, 2025)

Electrochemical flow-through membrane electrodes for sequential H* reduction and HO• oxidation of nitrobenzene - Zhaoyue Sun; Yingyun Qiao; Yujing Yue; Yunping Tong; Yuanyu Tian; Longgang Chu; Cheng Gu (Journal of Environmental Chemical Engineering, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Modified magnesium phosphate cement composed of hyaluronic acid and ultrasound-responsive nanocapsules with improved physicochemical and osteogenic properties - Junyan Yao; Bin Wang; Yanbin Zhao; Yingxi Xu; Cheng Wang; Jing Bai; Feng Xue; Paul K. Chu; Chenglin Chu (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Simultaneously calibrate and detect multiple analytes to offset the effects of co-existing regents and environmental fluctuations - Chu Cheng; Bingyan Jiang; Hongyu Chen; Xinyi Chen; Miao Lu (Analytica Chimica Acta, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Petrogenesis and tectonic significance of low-δ18O A-type granites in Nianzishan, Great Xing’an Range, NE China - Wen-Ting Zhang; Ying Wei; Ming-Xing Ling; Yi-Bo Zhao; Xi-Hui Cheng; Tian-Chu Chen (Journal of Asian Earth Sciences, 2025)

Dynamic variations in the volatile aromatic compound profile of jujube pulp during fermentation by mixed microbial cultures - Guangpeng Liu; Cheng Wang; Xueyao Lu; Nageena Qayyum; Xianhao Xu; Jiewei Tian; Yanrui Ma; Le Chu; Fatao He; Ye Song; Yuan Meng; Maoyu Wu; et al. (Food Chemistry, 2025)

Synergistic Cr(VI)/Oxytetracycline co-removal via acid-stable non-radical pathways enabled by plasmonic Z-scheme W18O49/Bi4NbO8Cl heterojunction - Chu-Jia Jin; Huai-Yuan Niu; Lei Ma; Ya-Ya Yang; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

Tough, adhesive, and conductive hydrogels enabled by stabilized PEDOT/sulfated cellulose dispersions for extreme-temperature sensing - Xiaowen Xie; Sirui Sun; Hong Wang; Yuezhen Hua; Zenghui Cheng; Juan Yu; Tongqi Yuan; Chunpeng Wang; Fuxiang Chu; Jifu Wang (Chemical Engineering Journal, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Enhanced thioether formation in stormwater pipes induced by nitrogen-containing pollutants: The role of the sediment microbiome - Fangyuan Jiang; Cheng Ye; Feifei Wang; Tianyi Dong; Jiazhi Wei; Zoran Kapelan; Jan Hofman; Zuxin Xu; Wenhai Chu (Bioresource Technology, 2025)

Effects and mechanisms of MSCs and MSC-derived exosomes in regulating ferroptosis - Zhiliang Guo; Zhuojian Qu; Yubing Zhang; Donghua Xu; Lijuan Chu; Min Cheng (Journal of Physiology and Biochemistry, 2025)

Bioaccumulation and Trophic Transfer of Polycyclic Aromatic Hydrocarbons (PAHs) in the Planktonic Base of the Aquatic Food Web - Jing-O. Cheng; Chi-Hung Chu; Chun-Wen Chang; Te-Hao Chen; Chi-Ying Hsieh; Fung-Chi Ko (Archives of Environmental Contamination and Toxicology, 2025)

Frequency adaptability analysis of typical acoustic propagation models - Ming Hui Li; Cheng Chen; Xiao Feng; Chu xiong Wang; Han yue Wang (Frontiers in Marine Science, 2025)
Underwater acoustic propagation is influenced by water column properties, seabed topography, and source frequency, with existing numerical models exhibiting varied performance across different conditions. This study evaluates the frequency adaptability of three acoustic models—BELLHOP (geometric ray-based), RAM (parabolic equation), and KRAKEN (coupled mode)—under diverse seabed topographies, including deep-sea-flat (25–2000 Hz), shallow-sea-flat (25–10000 Hz), and gentle/steep-slope seabed (25–800 Hz). Flat seabed scenarios use the Scooter model as a benchmark, while sloping seabed scenarios are compared against analytical solutions. Results indicate that in a 200 m deep flat ocean environment, BELLHOP achieves high accuracy for frequencies above 200 Hz, KRAKEN performs comparably to RAM below 50 Hz, and RAM excels below 200 Hz. In a 4000 m deep flat ocean, RAM outperforms at frequencies below 100 Hz, while BELLHOP performs well above 100 Hz. For sloping seabed environments with slopes less than 6.5°, RAM demonstrates stability below 100 Hz, while BELLHOP performs better above 100 Hz; for slopes greater than 6.5°, RAM remains stable below 50 Hz, with BELLHOP outperforming above 50 Hz. KRAKEN is found unsuitable for sloping seabed simulations. These findings provide quantitative guidance for selecting acoustic models based on frequency and seabed topography.

TsCYP94B1 regulates male fertility in androdioecious Tapiscia sinensis via jasmonic acid metabolism - Yujie Yang; Minggao Jiang; Peiyong Xin; Shujing Cheng; Jinfang Chu; Wenzhe Liu (Plant Science, 2025)

An innovative bioactive ingredient preparation method without column chromatography and gel filtration: High-purity 3S,3'S- astaxanthin from bioresources - Wei-Cheng Yuan; Tung-Ying Wu; Pei-Yi Chu; Fang-Rong Chang; Yang-Chang Wu (Phytochemistry Letters, 2025)

A novel phytogenic supplement that prevents coccidiosis in chickens - Ming-Chu Cheng; Yuan-Bin Cheng; Meng-Ting Chang; Chi-Ting Chang; Yu-Hsin Chen; Guan-Hua Lai; Hsing-Yu Liao; Yi-Yang Lien; Lie-Fen Shyur (Phytochemistry Letters, 2025)

Functional MTTP and apoB for VLDL secretion in chicken ovaries support small follicle development under heat stress - Petnamnueng Dettipponpong; Mei-Ying Sin; Yu-Hui Chen; Chuen-Yu Cheng; San-Yuan Huang; Rosemary L. Walzem; Ling-Chu Chang; Shuen-Ei Chen (Journal of Thermal Biology, 2025)

Thiols regulate photo-transformed fates of anthracene at surfaces of minerals: Potential roles of sulfhydryl in oxidative coupling of polycyclic aromatic hydrocarbons - Zhaoyue Sun; Xinghao Wang; Longgang Chu; Yunping Tong; Cun Liu; Guodong Fang; Hong Chen; Cheng Gu; Juan Gao (Journal of Hazardous Materials, 2025)

CO2 emissions associated with China's real estate development: 2000–2020 - Aishi Huang; Lei Zhang; Wenxuan Cheng; Gang Wang; Ming Chu; Tianhao Cai; Jia Jia (Journal of Environmental Sciences, 2025)

Covalent or non-covalent binding mechanisms of oligomeric proanthocyanidins with yeast proteins and the effects of different binding modes on the physicochemical, functional, and in vitro digestive of yeast protein - Jing-jing Fu; Qi-cheng Zhang; Xiang-yu Fu; Jing-chu Zhong; Xiao-yang Bai; Yue-wen Chen (Food Research International, 2025)

Elucidating the occurrence patterns of Alternaria toxin tenuazonic acid in individual tomatoes through MALDI-MSI and LC-MS/MS - Fan Sun; Yingying Fan; Yingying Dai; Muhai Tang; Jiangtao Du; Anqi Xu; Meichen Liu; Qianqian Chu; Dianzhen Yu; Ye Tian; Xiyan Sun; Weiheng Ren; et al. (Food Chemistry, 2025)

R-P phase high-entropy perovskite La0.5Sr1.5Mn0.2Fe0.2Ni0.2Cu0.2Co0.2O4 achieves complete PMS utilization via multi-pathway activation for efficient water purification - Lei Ma; Huai-Yuan Niu; Chu-Jia Jin; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Carbon nanotube/two-dimensional metal–organic framework composites with enhanced thermoelectric performances for thermoelectric generators - Cheng-Yuan Lin; Jhe-Wei Chang; Meng-Hao Lin; Kuan-Chu Wu; Shao-Huan Hong; Jhih-Min Lin; Chung-Wei Kung; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Hydrodepolymerization of lignin for the preparation of phenolic monomers, aromatic hydrocarbons, and cycloalkanes: Factors evaluation, mechanism analysis, and challenges - Bingbing Qiu; Donghui Zhang; Tian Cheng; Yanfang Wang; Huaqiang Chu (Chemical Engineering Journal, 2025)

Vismodegib Potentiates Marine Antimicrobial Peptide Tilapia Piscidin 4-Induced Cytotoxicity in Human Non-Small Cell Lung Cancer Cells - Wei-Chen Yeh; Yun-Chieh Tu; Tzu-Cheng Chien; Pei-Ling Hsu; Chu-Wan Lee; Shih-Ying Wu; Bo-Syong Pan; Hsin-Hsien Yu; Bor-Chyuan Su (Probiotics and Antimicrobial Proteins, 2025)

Attributing future changes in terrestrial evapotranspiration: The combined impacts of climate change, rising CO2, and land use change - Haiyan Hou; Xia Li; Yuanzhi Yao; Guohua Hu; Cheng Wang; Nan Chu (Agricultural and Forest Meteorology, 2025)

Fault Tectonic Characteristics of the Rift Trough Constrained by Gravity-Magnetic Anomalies - Meng-Long Xu; Zhen-Ning Su; Chu-Hao Feng; Tie Gao; Ya-Bin Yang; Cheng-Ye Sun; Lei Jing (Applied Geophysics, 2025)

Analysis of the shallow water bathymetric accuracy of ICESat-2 in combination with marine environmental factors - Sensen Chu; Ruihan Xu; Xuedong Zhang; Jian Cheng; Jizhe Li; Qixin Hu; Li Ye; Ziyang Qu (Marine Geodesy, 2025)

Analysis of sentinel-2 image time series for enhancing satellite-derived bathymetry - Qizhi Zhuang; Shanlin Gao; Yitong Liu; Zixuan Lu; Hengyong Chu; Jianbo Xiao; Jian Cheng; Qixin Hu; Sensen Chu (Marine Geodesy, 2025)

Hyperspectral Satellite-Derived Bathymetry Considering Substrate Characteristics - Li Ye; Sensen Chu; Hui Chen; Jian Cheng; Ruihan Xu; Ziyang Qu (Marine Geodesy, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Denitrification resilience and minimum phosphorus supplementation strategy for high-salinity desulfurization/denitrification wastewater under phosphorus limitation - Qinbiao Jiang; Wentao Yin; Shaohua Chu; Lijuan Feng; Zihan Tian; Zhijuan Tian; Junmei Cheng; Shuangshuang Jiang; Bu Li; Yanwen Yu (Journal of Water Process Engineering, 2025)

Galvanic effects between mackinawite and pyrogenic carbon: Enhancing radical-mediated ciprofloxacin transformation - Danning Lu; Longgang Chu; Haoran Yu; Zhaoyue Sun; Xiru Chen; Ruobing Wang; Xing Liu; Zhanghao Chen; Juan Gao; Cheng Gu (Journal of Hazardous Materials, 2025)

Enhanced removal of thioethers from stormwater pipe overflows by coagulation and oxidation treatment: Removal performance, reaction kinetics, and ecotoxicity - Jiazhi Wei; Fangyuan Jiang; Cheng Ye; Yayun Zhang; Zuxin Xu; Wenhai Chu (Journal of Hazardous Materials, 2025)

Variation in dietary preference related the per- and polyfluoroalkyl substance exposure in two sympatric seabird species from the Yellow Sea, China - Yachang Cheng; Yuanyuan Liu; Yuanyuan Zhao; Da Zheng; Kaize Feng; Jinye Cheng; Jiansong Chu; Yang Liu; Jiachen Sun (Journal of Hazardous Materials, 2025)

Novel supramolecular self-assembled nanomedicines for ultrasound-triggered tumor programmed therapy - Shumiao Tian; Tao Jiang; Min Su; Peixue Su; Zhekun Jia; Lang Ke; Yuhang Cheng; Yuxin Cao; Gang Liu; Chengchao Chu; Junxue Gao (Chemical Engineering Journal, 2025)

Rational design of methylthio-based self-assembled molecule for buried interface engineering in perovskite solar cells - Wenfei Chu; Haoran Yang; Xia Lei; Nan Yan; Fatemeh Arami Ghahfarokhi; Yuxiao Guo; Zhiqiang Guan; Zhimin Fang; Esmaeil Sheibani; Yuanhang Cheng; Bo Xu (Chemical Engineering Journal, 2025)

Corrigendum to “Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration” [chemical engineering journal 516 (2025) 1–22/CEJ_164176] - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

Integration of Ti3C2/TiO2 and spinel high-entropy oxide: A novel strategy for enhancing lithium-ion battery performance - Yingying Lu; Yi Zhang; Hailong Yan; Paul K. Chu; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low-valent Cu doping optimizes Ruddlesden-Popper perovskite for accelerated levofloxacin removal: Enhanced Ni-dominated dual radical/nonradical pathways - Lei Ma; Chu-Jia Jin; Huai-Yuan Niu; Zheng-Tao Dong; Long Sui; Qian Wu; Yan-Rong Peng; Jia-jia Wang; Cheng-Gang Niu (Journal of Hazardous Materials, 2025)

Proofreading of mismatches within primer-template junctions by Escherichia coli DNA polymerase I in vitro and in vivo - Hui-Lan Chang; Kang-Yi Su; Steven D. Goodman; Yung-Chu Chuang; Shen-Jyue Hsu; Yi-Kai Fang; Hsiao-Pei Yu; Cheng-Hao Fang; Ya-Chien Yang; Sui-Yuan Chang; Woei-horng Fang (DNA Repair, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Valorization of solid digestate through biochar production for toluene adsorption and enhanced energy recovery as solid recovered fuel - Shao-Fu Tu; Yu-Ming Chu; Tse-Lun Chen; Hsing-Cheng Hsi; Hwong-wen Ma; Yu-Chieh Ting (Waste Management, 2025)

Development of a flexible data assimilation system for a 3D unstructured-grid ocean model under Earth System Modeling Framework - Hao-Cheng Yu; Y. Joseph Zhang; Lars Nerger; Carsten Lemmen; Jason C.S. Yu; Tzu-Yin Chou; Chi-Hao Chu; Chuen-Teyr Terng (Ocean Modelling, 2025)

Simultaneous detection of citrus internal quality attributes using near-infrared spectroscopy and hyperspectral imaging with multi-task deep learning and instrumental transfer learning - Cheng Li; Chen Jin; Yuanning Zhai; Yuanyuan Pu; Hengnian Qi; Chu Zhang (Food Chemistry, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

Symmetry distortion engineering single-atom catalysts: Exceptional ORR activity and ultra-stable Zn-air batteries - Zhenghao Chen; Tsung-Cheng Yang; Chia-Min Yang; Cheng Bao; Zeyi Jiang; Shiqing Deng; Nien-Chu Lai (Chemical Engineering Journal, 2025)

Multi-interaction (substituted-phenylcarbamate)-hydroxypropyl-β-cyclodextrin chiral stationary phases for liquid chromatography - Junchao Zhu; Linna Xu; Wentao Xu; Huizhen Ni; Songlin Chen; Chu Chu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2025)

Emerging applications of fluorescence excitation-emission matrix with machine learning for water quality monitoring: A systematic review - Wancheng Cai; Cheng Ye; Feiyang Ao; Zuxin Xu; Wenhai Chu (Water Research, 2025)

Effects of pterostilbene on inducing apoptosis in normal bladder and bladder cancer cells - Chen-Hsun Ho; Chia-Kwung Fan; Yi-Chen Chu; Shih-Ping Liu; Po-Ching Cheng (Tissue and Cell, 2025)

Prophylactic effects of nirmatrelvir/ritonavir on reducing complications of cardiac surgery, reinfection, and post-acute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients with previous SARS-CoV-2 infection: a randomized clinical trial (PEP Trial) - Xin Yuan; Lihua Zhang; Jingkuo Li; Lubi Lei; Kai Chen; Qing Chu; Wei Feng; Xiaoqi Wang; Zhaoyun Cheng; Yan Yang; Yang Wang; Hansong Sun; et al. (Science Bulletin, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Precise fabrication of biochar nanosheets through CoAl-layered double hydroxide template-oriented effect for water decontamination via peroxymonosulfate activation - Chu-Chu Hu; Qi-E Zhang; Si-Cheng Hu; Si-Qin Guo; Yong-Xin Xin; Yan Pan; Jin-Gang Yu; Limin Lu; Guo-Qing Zhao (Journal of Environmental Management, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Exploring the degradation of ofloxacin in sewer overflows by Fe(Ⅵ)/PMS, Fe(Ⅵ)/PDS, and Fe(Ⅵ)/SPC: Overlooked synergistic effect of oxidation and in-situ coagulation - Qian Guo; Zuxin Xu; Wenhai Chu; Yingying Zhou; Xiaoting Gao; Cheng Ye (Journal of Hazardous Materials, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

The discharge of chlorinated effluent from wastewater treatment plants enhances dissolved oxygen in the receiving river: From laboratory study to practical application - Xueer Ren; Zuxin Xu; Wenhai Chu; Cheng Ye; Yingying Zhou; Jingyi Zhang; Qian Guo (Water Research, 2025)

Mycoplasma ovipnuemoniae impairs the immune response of sheep and suppresses neutrophil function by inhibiting S100A9 - Chenbo Yan; Tianning Dong; Yiyi Shan; Bingru Zhao; Hua Yang; Yu Cai; Shanglai Li; Qiuyue Liu; Yuefeng Chu; Huafang Hao; Zilong Cheng; Maojun Liu; et al. (Veterinary Microbiology, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Identifying priority habitat for future spatial conservation and management decisions of East Asian finless porpoise within Miaodao Archipelago waters, China - Yongtao Li; Zhongxun Wu; Yongzhong Chu; Zhaolong Cheng; Tao Zuo; Mingxiang Niu; Jun Wang (Marine Environmental Research, 2025)

Evidence for a command neuron controlling calling song in the cricket Gryllus assimilis - Chu-Cheng Lin; Berthold Hedwig (Journal of Insect Physiology, 2025)

Mercury pollution control and Marphysa sanguinea bio-response in active-capped sediment with calcium alginate/activated carbon composite - Che-Jung Hsu; Ying-Chu Wang; Adrienne Chung; Cheng-Di Dong; Chiu-Wen Chen; Yu Ting; Hsing-Cheng Hsi (Journal of Hazardous Materials, 2025)

Design and synthesis of uniform defective carbon nanosheets via CoAl-layered double hydroxide interlayer confinement for boosting peroxymonosulfate activation with highly efficient degradation of antibiotics contaminants - Qi-E. Zhang; Chu-Chu Hu; Si-Qin Guo; Jia-Wei Liu; Si-Cheng Hu; Yong-Xin Xin; Jin-Gang Yu; Guo-Qing Zhao; Limin Lu (Journal of Environmental Chemical Engineering, 2025)

Dynamic evaluation of China's atmospheric environmental pressure from 2008 to 2017: Trends and drivers - Aishi Huang; Ming Chu; Wenxuan Cheng; Gang Wang; Panbo Guan; Lei Zhang; Jia Jia (Journal of Environmental Sciences, 2025)

Bacteria-supported manganese oxide for enhanced fluoroquinolone antibiotics removal in peroxymonosulfate oxidation system - Ling Zhu; Yuan-Yuan Chu; Fei Liu; Kai-Yan Ai; Wen-Wen Xu; Yuan-Yuan Cheng; Chao Wu; Liu-Gen Zheng (Environmental Research, 2025)

Dysregulation of Iron Homeostasis Mediated by FTH Increases Ferroptosis Sensitivity in TP53-Mutant Glioblastoma - Xuejie Huan; Jiangang Li; Zhaobin Chu; Hongliang Zhang; Lei Cheng; Peng Lun; Xixun Du; Xi Chen; Qian Jiao; Hong Jiang (Neuroscience Bulletin, 2025)

Deep Learning with an Attention Mechanism for Enhancing Automated Modified Total Sharp/van der Heijde Scoring of Hand X-ray Images in Rheumatoid Arthritis - Chung-Yueh Lien; Hao-Jan Wang; Cheng-Kai Lu; Tzu-Hsuan Hsu; Woei-Chyn Chu; Chien-Chih Lai (Journal of Medical and Biological Engineering, 2025)
Purpose Rheumatoid arthritis (RA) is a chronic autoimmune disease whose accurate diagnosis relies on clinical symptoms, serological markers, and imaging studies, particularly X-ray evaluations of joint damage. A widely adopted metric for evaluating RA severity in hand and foot radiographs, the modified Total Sharp Score, quantifies joint erosion and joint space narrowing. However, manual scoring is labor-intensive, time-consuming, and prone to variability, limiting its reliability and consistency in clinical practice. Methods This study introduces a deep learning–based approach augmented with an attention mechanism to automate joint localization and damage classification in hand X-rays of patients with RA. The You Only Look Once v7 model was used for joint localization, incorporating performance enhancements via window-level transformation and the Distance Intersection over Union algorithm. Results The model achieved a localization accuracy of 99.66% mAP@0.50, significantly enhancing the detection precision. This model outperformed the vision transformer in scenarios involving limited data and small feature regions, achieving an overall classification accuracy of 88%. Conclusion The proposed method improved feature learning and classification, especially with limited data, and the attention mechanisms significantly enhanced the performance of the RA automatic diagnosis system. Data imbalance was effectively addressed via a modified EfficientNetV2 model with an integrated attention mechanism for joint damage classification.

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Cold stress changes the intestinal oxidative stress-mediated MAPK pathways and lipid metabolism in Takifugu fasciatus - Yuxi Liu; Xuechun Zang; Cheng Zhao; Peng Chu; Heyu Chen; Dongyong Fu; Sijin Wang; Kai Zhang; Tao Wang; Shaowu Yin (Aquaculture, 2025)

17α-methyltestosterone exposure disrupted growth, liver physiology and intestinal microbial on fish: A case study on migratory bony fishes (Takifugu fasciatus) - Yuxi Liu; Sijin Wang; Mengbo Han; Sheng Luo; Peng Chu; Xiaodong Tang; Cheng Zhao; Shiqun Han; Shaowu Yin; Tao Wang (Marine Pollution Bulletin, 2025)

Distribution characteristics of microplastics in surface waters in the western Pacific Ocean - Cheng Huo; Shoufeng Zhang; Ling Qu; Shuaichen Jin; Cijia Wang; Xiaoting Chu; Maowei Ju (Journal of Oceanology and Limnology, 2025)

Removal of single and multi-heavy metals from piggery digestate by the electric field-microalgae system: Influences, kinetics and mechanisms - Xiaosong Tian; Min Wang; Xing Liao; Shiyu Chu; Haixiang Cheng; Xiaoai Lin; Longzao Luo (Algal Research, 2025)

Blending of nitrogen-doped carbon nanotubes with transition metal: Effect of type and amount of metal seed on CO2 electroreduction to CO - Zihui Liu; Jiayi Cheng; Qiaoting Niu; Xiaoran Zhang; Juan Qian; Changqing Chu; Yan He (Journal of Environmental Chemical Engineering, 2025)

Large-Scale synthesis of crystalline phosphorus nanosheets with superior air-water stability and flame-retardancy ability - Zunbin Duan; Rui Li; He Bian; Yanfang Wang; Xue Zhang; Ziqiang Cheng; Danni Liu; Yang Li; Shuai Zhang; Guangbo Qu; Paul K. Chu; Jiahong Wang (Chemical Engineering Journal, 2025)

Thiosulfate-involved S-N biotransformation enables the long-term stability of a novel sulfur-cycle driven mainstream anammox process - Chu-Kuan Jiang; Yang-Fan Deng; Wen-Tao Tang; Cheng-Yu Xiao; Di Wu; Guang-Hao Chen (Chemical Engineering Journal, 2025)

FYB1-targeted modulation of CAPG promotes AML progression - Wenyuan Liu; Hongli Yin; Zhiwei Xie; Fang Fang; Jinhua Chu; Linhai Yang; Lingling Huang; Songji Tu; Huaju Cai; Zhengyu Wu; Anbang Wei; Chengzhu Liu; et al. (Molecular and Cellular Biochemistry, 2025)
Acute myeloid leukemia (AML) is a rare and heterogeneous disease. Over the past few decades, patient prognosis has improved with continuous improvements in treatment, but outcomes for some patients with primary drug resistance or relapse after treatment remain poor. Additional therapies to improve outcomes for these patients are urgently needed. FYB1 expression differs substantially between AML tissues and normal tissues. High FYB1 expression is correlated with poorer overall survival (OS), indicating that FYB1 may regulate AML progression. Therefore, understanding the effect of FYB1 on AML could improve the success rate of therapeutic approaches and prognosis for patients with AML. In this study, through analysis of large databases and both in vivo and in vitro experiments, we assessed the expression and role of FYB1 in AML and the relationship of FYB with patient prognosis. Downstream targets of the FYB1 gene were analyzed by RNA-seq. Database mining and in vitro experiments were used to further clarify the effect of the downstream target gelsolin-like actin-capping protein (CAPG) on AML cells and its relationship with patient prognosis. FYB1 expression was significantly higher in AML tissue and corresponded with a poor prognosis. FYB1 knockdown inhibited AML cell proliferation, promoted cell apoptosis, reduced cell adhesion capability and significantly reduced the tumor formation rate in mice. In addition, FYB1 knockdown induced a notable decrease in CAPG expression. The suppression of CAPG significantly inhibited cell proliferation and increased cell apoptosis. The conclusions of this study underscore the pivotal role of the FYB1/CAPG axis in promoting AML. We propose that the FYB1/CAPG axis could serve as a new thread in the development of therapeutic strategies for AML.

Dehydration, heavy metal removal patterns, and microbial response in high moisture copper-containing sludge composting assisted by electromagnetic techniques - X. Chu; G. Qu; H. Zou; M. Cheng; J. Li; N. Ren (International Journal of Environmental Science and Technology, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Advanced solar-driven hydrogel sponge for efficient heavy metal wastewater purification and clean water production through interfacial evaporation - Wencai Bai; Xingchuan Yang; Xiwang Song; Heyun Chu; Yong Xiang; Zhouxuan Zang; Changyuan Cheng; Chunmei Cao; Li Xu; Guoji Liu (Environmental Research, 2025)

FeS as hole transport pathway regulating charge transfer for efficient photoelectrochemical water splitting of hematite photoanodes - Shanshan Jiang; Miao Cheng; Dabo Liu; Ran Tao; Zhenming Chu; Xiaoxing Fan; Jie Guan (Chemical Engineering Journal, 2025)

Enhanced immune response with baculovirus-expressed BoHV-1 glycoprotein D in vaccine development - Nguyen-Thanh Hoa; Haroon Afzal; Uudamsaikhan Gundegmaa; Odbileg Raadan; Li-Ting Cheng; Chun-Yen Chu; Thu-Dung Doan; Yao-Chi Chung (The Veterinary Journal, 2024)

Transfer dynamics of antimicrobial resistance among gram-negative bacteria - Bangjuan Wang; Muhammad Haris Raza Farhan; Linlin Yuan; Yuxin Sui; Jinhua Chu; Xiaohan Yang; Yuxin Li; Lingli Huang; Guyue Cheng (Science of The Total Environment, 2024)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

A comprehensive review of critical factors affecting green ammonia synthesis by electrochemical process - Cheng-Yi Li; Shen-Wei Chu; Chia-Yun Ho; Han-Jung Chang; Terng-Jou Wan (Journal of Environmental Chemical Engineering, 2024)

Developing novel microwave-assisted induction heating (MAIH) technology for heating in-packaged ready-to-eat chicken breast products - Chiu-Chu Hwang; Yu-Ru Huang; Cheng-Da Hsieh; Yi-Chen Lee (Innovative Food Science & Emerging Technologies, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Machine learning-driven QSAR models for predicting the cytotoxicity of five common microplastics - Chengzhi Liu; Cheng Zong; Shuang Chen; Jiangliang Chu; Yifan Yang; Yong Pan; Beilei Yuan; Huazhong Zhang (Toxicology, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Multi-omics analysis reveals the genetic and environmental factors in shaping the gut resistome of a keystone rodent species - Guoliang Li; Dong Zhu; Chaoyuan Cheng; Haiyan Chu; Fuwen Wei; Zhibin Zhang (Science China Life Sciences, 2024)

Safety analysis code development and validation for lead-cooled fast reactor with helical coiled once-through steam generator - Jiaxin Zhang; Chenglong Wang; Wenxi Tian; G.H Su; Suizheng Qiu; Lin Xian; Kun Cheng; Xiao Chu; Shiying Wei; Guo Chen (Annals of Nuclear Energy, 2024)

Rapid detection of ingested acetaminophen on face mask by ambient ionization tandem mass spectrometry - Tiao-Lai Huang; Hung Su; Jia-Cheng Chen; Szu-Yu Kuo; Chia-Yi Hou; Shu-Yu Shih; Kuo-An Chu; Vinoth Kumar Ponnusamy; Chi-Wei Lee; Jentaie Shiea (Analytica Chimica Acta, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Immune response and protection efficacy of formalin‐killed vaccines against Streptococcus iniae in four‐finger threadfin Eleutheronema tetradactylum - Yin‐Ze Shi; Andre Giovanni; Li‐Wu Cheng; Wen‐Rou Huang; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Four‐finger threadfin, Eleutheronema tetradactylum farming in southern Taiwan has been facing disease problems caused by Streptococcus iniae since 2018. The development of a vaccine against infectious S . iniae in the cultured threadfin industry is necessary. Thus, this study aimed to examine the efficacy of threadfin immunized formalin‐killed cells (FKC) from S . iniae GSI‐111 for 42 days post‐vaccination (dpv) using two doses of FKC alone (a booster at 14 dpv) as group A, and FKC mixed with ISA763A adjuvant using a single dose as group B or double doses as group C. Immunoglobulin (Ig)‐M was purified from threadfin, and rabbit anti‐threadfin IgM polyclonal antibodies were used to detect antibody level in immunized fish; the vaccinated group A displayed higher levels at 3 dpv and all vaccinated treatments demonstrated high antibody levels between 14 and 42 dpv. All vaccine groups showed significantly higher values of lysozyme activity at 42 dpv compared with the control group; the vaccinated A group peaked at 14 dpv. The expression profiles of pro‐inflammatory and immune‐related genes, TNF‐α , IL‐12A , and C2 were upregulated at 3 dpv, while CD8A and chemokine receptor CXCR4 were upregulated at 42 dpv. Finally, the threadfins were challenged with S . iniae at 42 dpv. The average relative percent survival was 96% for vaccination A and B treatments, and 100% for vaccination C treatment. In summary, this study demonstrated that FKC vaccines whether formulated with an adjuvant could stimulate immune response and effective protect threadfins against S . iniae infection.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Long–term exposure to particulate matter pollution and incidence of ischemic and hemorrhagic stroke: A prospective cohort study in Eastern China - Li Yang; Menghao Wang; Cheng Xuan; Caiyan Yu; Yixiang Zhu; Huihuan Luo; Xia Meng; Su Shi; Yali Wang; Hongjie Chu; Renjie Chen; Jing Yan (Environmental Pollution, 2024)

Associations between exposure to brominated flame retardants and periodontitis in U.S. adults - Jia-jie Lv; Shu-yue Li; Xiang-meng Kong; Yan Zhao; Xin-yu Li; Hong Guo; Chu Feng; Cheng-hao Yang (Chemosphere, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

New insights and reaction mechanisms in the design of catalysts for the synergistic removal of NO and VOCs from coke oven flue gas: Dual regulation of oxidative properties and acidic sites - Zimo Chen; Cheng Zhao; Ninghan Wei; Junge Yun; Rencheng Chu; Han Zheng; Xin Feng; Zhangfa Tong; Zhihang Chen (Journal of Hazardous Materials, 2024)

Interannual variation of the westward ridge point of the Western Pacific subtropical high in boreal winter - Shu Gui; Jinxin Cheng; Ruowen Yang; Qiulan He; Zizhen Dong; Ji Ma; Qucheng Chu; Meiyi Hou (Global and Planetary Change, 2024)

Analysis of flavor substances changes during fermentation of Chinese spicy cabbage based on GC-IMS and PCA - Wenkui Guo; Meiru Cheng; Xuemei Dong; Chuan Liu; Yu Miao; Peng Du; Hong Chu; Chun Li; Libo Liu (Food Research International, 2024)

Nanoscale characterization of Ediacaran microfossils from lower Doushantuo formation chert nodules - Shiqi Cheng; Lianjun Feng; Chaoqun Zhang; Linhao Cui; Wei Liu; Hao Qiu; Shi He; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2024)

Comparative pathogenicity and histopathological analysis of Edwardsiella anguillarum intraperitoneal infection in milkfish ( Chanos chanos ), Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Edwardsiella anguillarum , a highly virulent species within the Edwardsiella genus, causes significant mortality in milkfish farms in Taiwan. This study aimed to investigate the comparison of milkfish susceptibility, a newly identified host species in Taiwanese aquaculture, with other species Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ), to E. anguillarum , elucidating its pathogenicity across both seawater and freshwater aquaculture environments. The results showed milkfish exhibited the highest mortality rate of 85% within 48 h of infection, whereas Nile tilapia exhibited a mortality rate of 70% between the second‐ and tenth‐day post challenge, and seabass exhibited a mortality rate of 25% between the second‐ and sixth‐day post challenge. Gross lesions observed in milkfish included splenomegaly and haemorrhage, whereas Nile tilapia exhibited signs of ascites, exophthalmia and brain haemorrhage. Seabass displayed spleen granulomas and haemorrhage at the injection site. Histopathological analysis revealed common features across all three species, including multifocal necrosis, bacterial presence in the necrotic areas, serositis and oedema. Asian seabass also exhibited chronic lesions in the form of splenic granulomas. This study highlights the high susceptibility of milkfish and Nile tilapia to E. anguillarum , emphasizing the urgent need for further investigation into targeted vaccine development for these fish species. These results not only deepen our understanding of the differing levels of pathogenicity among the three species but also offer valuable insights for improving disease prevention and management strategies in aquaculture, including those applied within polyculture systems and for the maintenance of aquaculture water environments.

Numerical Simulation of Flow Field around Jacket Foundations on Flat-Bed and Equilibrium Scour Bathymetry - Dawei Guan; Yinuo Chu; Cheng Chen; Jingang Liu; Zishun Yao (Journal of Marine Science and Engineering, 2024)
In recent years, jacket foundations have been increasingly employed in offshore wind farms. Their complex design comprising piles and trusses poses challenges for conducting comprehensive flow field measurements using physical experiments. Consequently, the influence of the flow field on local scour around these foundations remains unclear. Therefore, numerical simulation methods are essential to depict the surrounding flow characteristics. This study utilizes large eddy simulation (LES) turbulence models within OpenFOAM to simulate the flow field around jacket foundations on flat-bed and equilibrium scour bathymetry. A flume experiment was conducted for numerical model establishment and validation. The close agreement between experimental and numerical results indicates that the LES model accurately reflects the flow patterns around the jacket foundation. Time-averaged and instantaneous flow characteristics, average kinetic energy (AKE), turbulence structure, and bed shear stress were analyzed. The results indicate that flow intensity is reduced due to the shielding effect and energy dissipation by the truss structure of the jacket foundation. Furthermore, the AKE of the flow upstream of the rear piles decreases by 18.9% in the flat-bed state and 28.0% in the equilibrium state, indicating more energy dissipation and less scour at the rear piles in the equilibrium state. The research findings offer valuable insights into the design and scour protection strategies for jacket foundations.

Properties and Model of Pore-Scale Methane Displacing Water in Hydrate-Bearing Sediments - Dongfeng Ge; Jicheng Zhang; Youxun Cao; Cheng Liu; Bin Wu; Haotian Chu; Jialin Lu; Wentao Li (Journal of Marine Science and Engineering, 2024)
The flow characteristics of methane and water in sedimentary layers are important factors that affect the beneficial exploitation of marine hydrates. To study the influencing factors of methane drive-off water processes in porous media, we constructed nonhomogeneous geometric models using MATLAB 2020a random distribution functions. We developed a mathematical model of gas–water two-phase flow based on the Navier–Stokes equation. The gas-driven water processes in porous media were described using the level-set method and solved through the finite element method. We investigated the effects of the nonhomogeneous structure of pore media, wettability, and repulsion rate on gas-driven water channeling. The nonhomogeneity of the pore medium is the most critical factor influencing the flow. The size of the throat within the hydrophilic environment determines the level of difficulty of gas-driven water flow. In regions with a high concentration of narrow passages, the formation of extensive air-locked areas is more likely, leading to a decrease in the efficiency of the flow channel. In the gas–water drive process, water saturation changes over time according to a negative exponential function relationship. The more hydrophilic the pore medium, the more difficult the gas-phase drive becomes, and this correlation is particularly noticeable at higher drive rates. The significant pressure differentials caused by the high drive-off velocities lead to quicker methane breakthroughs. Instantaneous flow rates at narrow throats can be up to two orders of magnitude higher than average. Additionally, there is a susceptibility to vortex flow in the area where the throat connects to the orifice. The results of this study can enhance our understanding of gas–water two-phase flow in porous media and help commercialize the exploitation of clean energy in the deep ocean.

Synthesis of N-vinylcarbazole from acetylene by a continuous high-pressure liquid-phase process with inherent safety - Yao Mu; Jiahe Fan; Bozhao Chu; Siqing Zhong; Yi Cheng (Chemical Engineering Journal, 2024)

Bioinspired Polarized Optical Flow Enables Turbid Underwater Target Motion Estimation - Haoyuan Cheng; Shujie Zhao; Jinchi Zhu; Hao Yu; Jinkui Chu (Journal of Ocean University of China, 2024)

Advancing illicit connection diagnosis of urban stormwater pipes: Comprehensive analysis with EEM fluorescence spectroscopy - Feiyang Ao; Cheng Ye; Yilin Xu; Zhengdi Wu; Zuxin Xu; Wenhai Chu (Water Research, 2024)

Integrating quantitative microbiological risk assessment and disability-adjusted life years to evaluate the effects of urbanization on health risks for river recreationists - Cheng-Shin Jang; Chu-Chih Liu (Science of The Total Environment, 2024)

Green supply chain for steel raw materials under price and demand uncertainty - Cong Cheng; HongMei Chu; Liang Zhang; LianJie Tang (Journal of Cleaner Production, 2024)

Comparative pathogenicity of Nocardia seriolae in Nile tilapia ( Oreochromis niloticus ), milkfish ( Chanos chanos ) and Asian seabass ( Lates calcarifer ) - Sandra Celenia Nazareth; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Nocardiosis, caused by Nocardia seriolae , has been a prominent disease in Southeast Asian aquaculture in the last three decades. This granulomatous disease reported in various fish species is responsible for significant economic losses. This study investigated the pathogenicity of N. seriolae in three cultured species in Taiwan: Nile tilapia (omnivore), milkfish (herbivore) and Asian seabass (carnivore). Administration of an infective dose of 1 × 10 6 CFU/ fish in tilapia, seabass and milkfish demonstrated mortalities of 100%, 90% and 75%, respectively. Additionally, clinical signs namely, granuloma and lesions displayed varying intensities between the groups and pathological scores. Polymerase chain reaction (PCR) amplification specific for N. seriolae was confirmed to be positive (432 bp) using NS1/NG1 primers. Post‐mortem lesions revealed the absence of granulomas in tilapia and milkfish and their presence in the seabass. Interestingly, the gut in tilapia showed an influx of eosinophils suggesting its role during the acute stages of infection. However, post‐challenge, surviving milkfish exhibited granulomatous formations, while surviving seabass progressed toward healing and tissue repair within sampled tissues. Overall, in conclusion, these results demonstrate the versatility in the immunological ability of individual Perciformes to contain this pathogen as a crucial factor that influences its degree of susceptibility.

Marine Radar Oil Spill Detection Method Based on YOLOv8 and SA_PSO - Jin Xu; Yuanyuan Huang; Haihui Dong; Lilin Chu; Yuqiang Yang; Zheng Li; Sihan Qian; Min Cheng; Bo Li; Peng Liu; Jianning Wu (Journal of Marine Science and Engineering, 2024)
In the midst of a rapidly evolving economic landscape, the global demand for oil is steadily escalating. This increased demand has fueled marine extraction and maritime transportation of oil, resulting in a consequential and uneven surge in maritime oil spills. Characterized by their abrupt onset, rapid pollution dissemination, prolonged harm, and challenges in short-term containment, oil spill accidents pose significant economic and environmental threats. Consequently, it is imperative to adopt effective and reliable methods for timely detection of oil spills to minimize the damage inflicted by such incidents. Leveraging the YOLO deep learning network, this paper introduces a methodology for the automated detection of oil spill targets. The experimental data pre-processing incorporated denoise, grayscale modification, and contrast boost. Subsequently, realistic radar oil spill images were employed as extensive training samples in the YOLOv8 network model. The trained detection model demonstrated rapid and precise identification of valid oil spill regions. Ultimately, the oil films within the identified spill regions were extracted utilizing the simulated annealing particle swarm optimization (SA-PSO) algorithm. The proposed method for offshore oil spill survey presented here can offer immediate and valid data support for regular patrols and emergency reaction efforts.

Sand resource extraction from waste soils based on the hydro-cyclone separation principle - Xiangru Chu; Guohui Yuan; Ning Fan; Shihu Gao; Zeping Cheng (Marine Georesources & Geotechnology, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Novel chitosan-modified biochar prepared from a Chinese herb residue for multiple heavy metals removal: Characterization, performance and mechanism - Chengjiu Wang; Jixu Qiao; Jiandan Yuan; Zhentao Tang; Tianzhe Chu; Ruifeng Lin; Hongting Wen; Chuan Zheng; Hulan Chen; Haijiao Xie; Cheng Peng; Yuzhu Tan (Bioresource Technology, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Investigation of Pore Structure and Adsorption/Desorption Properties of Coal in the Non-uniform Stress Zone: Implications for Coal and Gas Outburst - Zhuang Lu; Liang Wang; Songwei Wu; Peng Chu; Chuanpeng Xi; Hao Wang; Yuanping Cheng (Natural Resources Research, 2024)

Facilitating effects of the synergy with zero-valent iron and peroxysulfate on the sludge anaerobic fermentation system: Combined biological enzyme, microbial community and fermentation mechanism assessment - Baodan Jin; Yusheng Jia; Ken Cheng; Chenchen Chu; Jiacheng Wang; Ye Liu; Jingjing Du; Lan Wang; Long Pang; Jiantao Ji; Xia Cao (Chemosphere, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Iron-containing nanominerals for sustainable phosphate management: A comprehensive review and future perspectives - Teng Bao; Mekdimu Mezemir Damtie; Chu Yan Wang; Cheng Long Li; Zhijie Chen; Kuk CHO; Wei Wei; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Science of The Total Environment, 2024)

Short-term cooling load prediction for central air conditioning systems with small sample based on permutation entropy and temporal convolutional network - Ning He; Lijun Zhang; Cheng Qian; Feng Gao; Ruoxia Li; Fuan Cheng; Danlei Chu (Energy and Buildings, 2024)

Mechanism of Paris polyphylla saponin II inducing autophagic to inhibit angiogenesis of cervical cancer - Hui Cheng; Jiao Long; Jingjing Su; Jing Chu; Meng Wang; Qinglin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Submarine Morphological Description of the Ancient Archipelagic Aprons in the Marcus–Wake Seamount Group, Northwestern Pacific Ocean - Xiao Wang; Huaiming Li; Yongshou Cheng; Pengfei Yao; Fengyou Chu; Weilin Ma; Hongyi Wang; Shihui Lv; Xiaohu Li; Zhenggang Li; Weiyan Zhang; Yanhui Dong (Journal of Marine Science and Engineering, 2024)
Herein, the morphological characteristics of submarine archipelagic aprons were presented for five guyots, Suda, Arnold, Lamont, Niulang, and Zhinyv, which are over 80 Ma years old and are located in the Marcus–Wake seamount group, northwestern Pacific Ocean. Nearly 28 landslide deposits were recognized using the bathymetry and backscatter intensity data collected from the studied guyots. Landslides and their deposits that surround seamounts are mostly related to the morphology of debris avalanches, scarps, gullies/channels, and bedforms. The morphology of the archipelagic aprons of the studied guyots indicates mutual landslide processes, including slump and distinct debris avalanches arising from a cohesive or cohesionless landslide material flow. The superimposition of debris flows and sedimentation dominates the recent stages of the studied guyots. The archipelagic aprons corresponding to convex-arc-shaped scarps exhibit larger domains compared to the invagination-arc-shaped scarps with similar lateral lengths. The scarp morphologies of the studied guyots are predominantly of the complex-arc shape, indicating multiple landslide events. Parallel and convergent gullies and channels are mostly found on the elongated landslide deposits, whereas divergent and radial gullies and channels are mostly distributed on the fan-shaped aprons. Ubiquitous sediment waves occurred on the bedforms of the distal archipelagic apron across the studied guyots because of sediment creep. Small-scale sediment waves were only observed in the channels on the aprons of the Suda guyot.

The formation and control of disinfection by-products by two-step chlorination for sewage effluent: Role of organic chloramine decomposition among molecular weight fractions - Cheng Ye; Di Zhang; Chao Fang; Jimeng Ding; Youli Duan; Wenhai Chu (Water Research, 2024)

Scenario modeling method for collision avoidance testing in inland waterway - Hai-ming Zhou; Mao Zheng; Xiu-min Chu; Chen-guang Liu; Cheng Zhong (Ocean Engineering, 2024)

Tomato CYP94C1 inactivates bioactive JA-Ile to attenuate jasmonate-mediated defense during fruit ripening - Tianxia Yang; Lei Deng; Qinyang Wang; Chuanlong Sun; Muhammad Ali; Fangming Wu; Huawei Zhai; Qian Xu; Peiyong Xin; Shujing Cheng; Jinfang Chu; Tingting Huang; et al. (Molecular Plant, 2024)

Current status of research on microbial electrocatalytic CH4 production for biogas upgrading and challenges - Xiaomei Chu; Yuanchuan Ren; Guangfei Qu; Nanqi Ren; Ruosong Xie; Minhua Cheng; Xiuping Chen; Zuoliang Wang; Yongheng Yuan (Journal of Environmental Chemical Engineering, 2024)

3-D visual analysis and quantitative characterization on coal matrix based on Micro-CT - Changxin Zhao; Yuanping Cheng; Chenghao Wang; Kaizhong Zhang; Zhenyang Wang; Peng Chu; Tao Yang (International Journal of Rock Mechanics and Mining Sciences, 2024)

A comprehensive attribution analysis of PM2.5 in typical industrial cities during the winter of 2016–2018: Effect of meteorology and emission reduction - Aishi Huang; Wenxuan Cheng; Ming Chu; Gang Wang; Heyang Yang; Lei Zhang (Atmospheric Research, 2024)

Cenozoic structural and tectonic evolution in the Western Xihu Basin, East China Sea Shelf Basin - Bin Xu; Zhiping Wu; Yanjun Cheng; Johannes M. Miocic; Yining Dai; Yichen Chu (International Journal of Earth Sciences, 2024)

Overexpression of Nrf2 reverses ferroptosis induced by Arenobufagin in gastric cancer - Jiao Long; Wenjun Wang; Jing Chu; Yueyue Li; Meng Wang; Jingjing Su; Yuting Yang; GuoKai Wang; Qinglin Li; Hui Cheng (Toxicology and Applied Pharmacology, 2024)

Preparation of nitrogen-doped activated carbon used for catalytic oxidation removal of H2S - Shanjie Cheng; Tao Wang; Liang Chu; Jun Li; Liqiang Zhang (Science of The Total Environment, 2024)

Additive manufacturing of broadband electromagnetic wave absorbing materials: Polymer-derived SiC/Si3N4 composites with triply periodic minimal surface meta-structure - Siwen Yu; Chaochao Wang; Zuzheng Chen; Zhuohao Qiu; Chengyi Chu; Yuchuan Cheng; Tao Zeng; Aihua Sun (Chemical Engineering Journal, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

Tracking the source of antibiotic resistome in the stormwater network drainage in the presence of sewage illicit connections - Yu Zhang; Zuxin Xu; Wenhai Chu; Jingyi Zhang; Wei Jin; Cheng Ye (Science of The Total Environment, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Ultralow-Concentration (0.1M) Electrolyte for stable bulk alloy (Sn, Bi) anode in Sodium-ion battery via Regulating Anions Structure - Changting Chu; Lin Zhou; Yong Cheng; Xuxu Wang; Limin Chang; Ping Nie; Chunli Wang; Limin Wang (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Viburnum odoratissimum and their chemotaxonomic significance - Cheng-Yu Chu; Shi-Fang Li; Xiao-Xiao Huang; Shao-Jiang Song (Biochemical Systematics and Ecology, 2024)

An Uncertainty Analysis Method Based on a Globally Optimal Truth Discovery Model for Mineral Prospectivity Mapping - Nan Li; Shitao Yin; Cangbai Li; Yishi Wang; Keyan Xiao; Rui Cao; Weihua Hua; Wenkai Chu; Xianglong Song; Cheng Li (Mathematical Geosciences, 2024)

Review on the reproductive biology of the Takifugu genus and its application in sex control - Cheng Zhao; Peng Chu; Yuxi Liu; Sijin Wang; Tao Wang; Shaowu Yin (Aquaculture, 2024)

The impact of extremely low-temperature changes on fish: A case study on migratory bony fishes (Takifugu fasciatus) - Peng Chu; Sijin Wang; Weifeng Yu; Aling Wang; Yongqin Zong; Shaowu Yin; Cheng Zhao; Tao Wang (Aquaculture, 2024)

Redox property of coordinated iron ion enables activation of O2 via in-situ generated H2O2 and additionally added H2O2 in EDTA-chelated Fenton reaction - Yuan Gao; Pengyi Wang; Yu Chu; Fan Kang; Yue Cheng; Eveliina Repo; Mingbao Feng; Xin Yu; Huabin Zeng (Water Research, 2024)

Paris polyphylla saponins II inhibits invasive, migration and epithelial-mesenchymal transition of melanoma cells through activation of autophagy - Hui Cheng; Jing Chu; Yuting Yang; Yueyue Li; Meng Wang; Huan Wu; Manman Wang; Jingjing Su; Qinglin Li (Toxicon, 2024)

An autonomous coverage path planning algorithm for maritime search and rescue of persons-in-water based on deep reinforcement learning - Jie Wu; Liang Cheng; Sensen Chu; Yanjie Song (Ocean Engineering, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Integrated analysis of transcriptome, translatome and proteome reveals insights into yellow catfish (Pelteobagrus fulvidraco) brain in response to hypoxia - Cheng Zhao; Yubing Ding; Yufei Zhang; Mingxu Chu; Xianhui Ning; Jie Ji; Tao Wang; Guosong Zhang; Shaowu Yin; Kai Zhang (Aquatic Toxicology, 2024)

Identification of chrysanthemum using hyperspectral imaging based on few-shot class incremental learning - Zeyi Cai; Mengyu He; Cheng Li; Hengnian Qi; Ruibin Bai; Jian Yang; Chu Zhang (Computers and Electronics in Agriculture, 2023)

Simultaneous detection and removal of mercury (II) using multifunctional fluorescent materials - Xiang Cheng; Ting Luo; Feiyi Chu; Bin Feng; Shibo Zhong; Fei Chen; Jie Dong; Wenbin Zeng (Science of The Total Environment, 2023)

Simultaneous modulation of CHO cell cytotoxicity, turbidity, and DOC by coagulation with or without pre-oxidation in water from the Pearl River Delta region, China - Hongyu Du; Tianle Cheng; Wenhai Chu; Xiao Wei; Xiaohong Chen; Bingjun Liu; Kyu Hur; Shengkun Dong (Science of The Total Environment, 2023)

Harmonization of semi-objective ANP with explained CRITIC for quantitative evaluation of fire hazard risks for flame-retardant materials - Bin Zou; Xin Wang; Jiajun Li; Zhenfeng Cheng; Guotao Ye; Wenhao Yang; Liangyuan Qi; Pengfei Jia; Fukai Chu; Zetao Xiao; Lei Song; Zhou Gui; et al. (Process Safety and Environmental Protection, 2023)

Mechanism study on a novel Cu/Fe co-catalyzed heterogeneous particle mediated activation of hydrogen peroxide for efficient degradation of cyanides - Xiuping Chen; Ting Zhang; Guangfei Qu; Yuanchuan Ren; Zuoliang Wang; Jun Wang; Ping Lu; Minhua Cheng; Xiaomei Chu (Journal of Water Process Engineering, 2023)

Effect of design parameters on degree of blending and performance of recycled hot-mix asphalt incorporating fine reclaimed asphalt pavement particles - Yining Zhang; Wenkai Zhu; Xiaolong Chu; Haidong Dong; Dong Liu; Yanyan Liu; Hengjin Chen; Huailei Cheng; Lijun Sun (Journal of Cleaner Production, 2023)

Highly flexible multilayer MXene hollow carbon nanofibers confined with Fe3C particles for high-performance lithium-ion batteries - Xiaohong Lu; Jinbing Cheng; Dawei Zhou; Yichong Chen; Hao Jiang; Yang Lu; Deyang Zhang; Dezhi Kong; Paul K. Chu; Hui Ying Yang; Yongsong Luo (Chemical Engineering Journal, 2023)

Microplastics enrichment characteristics of antibiotic resistance genes and pathogens in landfill leachate - Cheng Qiu; Yiwei Zhou; Hua Wang; Yixuan Chu; Lei Zheng; Yongmin Chen; Yali Song; Chengran Fang (Chemosphere, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Zircon U–Pb geochronology, Hf–O isotopes and whole-rock geochemistry of A-type granitoids in Halajun, South Tienshan, NW China: Implications for subdivision, petrogenesis and tectonic settings - Tian-Chu Chen; Ming-Xing Ling; Yu-Long Liu; Ying Wei; Xi-Hui Cheng; Xiao-Yan Jiang; Shuo Xue; Ze-Bin Luo; Jiang-Hao Bai (Lithos, 2023)

Investigation of renewable methanol production from CO2 hydrogeneration based on spectral splitting and heat integration - Yuhang Li; Yue Hu; Jiankang Chu; Yucheng Yao; Hui Lv; Cheng Xu (Fuel, 2023)

Carrier-free 5-Fu nanoparticle-mediated domestication therapy for scar treatment: A preclinical and first-in-human study - Peng He; Sha Yi; Jianzhong Zhang; Chengchao Chu; Xuqi Peng; Changhong Li; Xinfei Sun; Yang Zhang; Hongwei Cheng; Xia Xiong; Gang Liu (Chemical Engineering Journal, 2023)

Pathogenicity characterization of nocardiosis in orange‐spotted grouper ( Epinephelus coioides ) via exposure to nine distinct isolates of Nocardia seriolae and four administrative routes - Phuong Nguyen; Andre Giovanni; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Nocardia seriolae causes chronic nocardiosis in various marine and freshwater aquatic animals; however, grouper species have rarely been investigated. This study evaluated the pathogenicity of nocardiosis following N. seriolae infection in the orange‐spotted grouper Epinephelus coioides . Nine identified genetic isolates of N. seriolae were tested in vivo using the intraperitoneal method and observed daily for 35 days. The most virulent isolate was then used to evaluate transmission through different routes (intraperitoneal IP, intramuscular IM, oral OR, and immersion IS) in the same fish model and was observed daily for 42 days. The results showed mild variation in virulence among N. seriolae isolates. AOD107132‐2 K and OT103003‐N11 strains displayed the highest and lowest risk virulence, respectively, based on the accumulation and kinetics of mortality. IM and IP administrations showed an early phase response with early mortality by 5 dpc (30%–100%), while slower kinetics of nocardiosis occurred in the OR and IS routes with slow mortality at 35 dpc (4%–8%). Histopathology revealed typical granulomas, confirming the progression of nocardiosis in the diseased fish. These results provide the basis for further studies on the virulence profile of N. seriolae in Taiwan and a well‐suited route of administration in orange‐spotted groupers for further prevention development.

Genotypic and phenotypic analysis of Elizabethkingia meningoseptica in bullfrog Rana catesbeiana isolated in Taiwan - Ming‐An Tsai; Ming She See; Cheng‐Hsun Chiu; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Elizabethkingia meningoseptica is a hazardous bacterium for agriculture production and human health. The present study identified E. meningoseptica from the bullfrog, human and reference strain BCRC 10677 by API 20NE, 50S ribosome protein L27 sequencing and pulse field gel electrophoresis to differentiate isolates of E. meningoseptica from aquatic animals and humans. All isolates from bullfrogs and humans were identified as E. meningoseptica by DNA sequencing with 98.8%–100% sequence identity. E. meningoseptica displayed significant genetic diversity when analysed using pulsed‐field gel electrophoresis (PFGE). There were six distinct pulsotypes, including one pulsotype found in bullfrog isolates and five pulsotypes found in human isolates. However, E. meningoseptica from bullfrog exhibited one genotype only by PFGE. Overall, molecular epidemiological analysis of PFGE results indicated that the frog E. meningoseptica outbreaks in Taiwan were produced by genetically identical clones. The bullfrog isolates were not genetically related to other E. meningoseptica from human and reference isolates. This research provided the first comparisons of biochemical characteristics and genetic differences of E. meningoseptica from human and bullfrog isolates.

Responses of applied voltages on the archaea microbial distribution in sludge digestion - Yingying Cai; Heng Li; Guangfei Qu; Yinghui Hu; Hongmei Zou; Shiqiang Zhao; Minhua Cheng; Xiaomei Chu; Nanqi Ren (Chemosphere, 2023)

Study on the mechanism of rapid degradation of Rhodamine B with Fe/Cu@antimony tailing nano catalytic particle electrode in a three dimensional electrochemical reactor - Yuanchuan Ren; Ping Lu; Guangfei Qu; Ping Ning; Nanqi Ren; Jun Wang; Fenghui Wu; Xiuping Chen; Zuoliang Wang; Ting Zhang; Minhua Cheng; Xiaomei Chu (Water Research, 2023)

Assessing water quality in the Pearl River for the last decade based on clustering: Characteristic, evolution and policy implications - Jiang Wu; Shu-Peng Cheng; Ling-Yan He; Yi-Chu Wang; Yao Yue; Hui Zeng; Nan Xu (Water Research, 2023)

Secondary aerosol formation in incense burning particles by O3 and OH oxidation via single particle mixing state analysis - Zhancong Liang; Liyuan Zhou; Xinyue Li; Rosemarie Ann Infante Cuevas; Rongzhi Tang; Mei Li; Chunlei Cheng; Yangxi Chu; Patrick K.H. Lee; Alvin C.K. Lai; Chak K. Chan (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Identification of geographical origins of Radix Paeoniae Alba using hyperspectral imaging with deep learning-based fusion approaches - Zeyi Cai; Zihong Huang; Mengyu He; Cheng Li; Hengnian Qi; Jiyu Peng; Fei Zhou; Chu Zhang (Food Chemistry, 2023)

Pivotal role of Boron-doped graphene quantum dots in stretchable and Self-Healable red emission nanocomposite Film: One step advance for white light emitting diodes application - Chen-Chu Hsu; Livy Laysandra; Yu-Cheng Chiu; Wei-Ren Liu (Chemical Engineering Journal, 2023)

Reevaluation for UV photolysis of Fe(III) inducing tetracycline abatement: Overlooked significance of complexation-assistance in environmental fates of antibiotics - Xin Cheng; Jingquan Wang; Bo Yang; Chengjin Wang; Wenhai Chu; Hongguang Guo (Journal of Hazardous Materials, 2023)

Exposure to copper nanoparticles or copper sulfate dysregulated the hypothalamic-pituitary-gonadal axis, gonadal histology, and metabolites in Pelteobagrus fulvidraco - Cheng Zhao; Peng Chu; Xiaodong Tang; Jie Yan; Xiaomen Han; Jie Ji; Xianhui Ning; Kai Zhang; Shaowu Yin; Tao Wang (Journal of Hazardous Materials, 2023)

Black phosphorus nanosheets enhance differentiation of neural progenitor cells for improved treatment in spinal cord injury - Fumei He; Ke Cheng; Junyang Qi; Fangjie He; Chengjun Chu; Yue Xiong; Jingxin Zhao; JiaQi Ding; FanShu Kong; ZiMeng Cao; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

MRI radiomics for brain metastasis sub-pathology classification from non-small cell lung cancer: a machine learning, multicenter study - Fuxing Deng; Zhiyuan Liu; Wei Fang; Lishui Niu; Xianjing Chu; Quan Cheng; Zijian Zhang; Rongrong Zhou; Guang Yang (Physical and Engineering Sciences in Medicine, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Copper induced intestinal inflammation response through oxidative stress induced endoplasmic reticulum stress in Takifugu fasciatus - Sisi Ma; Yuxi Liu; Cheng Zhao; Peng Chu; Shaowu Yin; Tao Wang (Aquatic Toxicology, 2023)

Aberrant Histone Modification of TNFAIP3, TLR4, TNIP2, miR-146a, and miR-155 in Major Depressive Disorder - Chu-Chiao Tseng; Shao-Cheng Wang; Yi-Chien Yang; Hung-Chun Fu; Chen-Kai Chou; Hong-Yo Kang; Yi-Yung Hung (Molecular Neurobiology, 2023)

Oral and inhalation bioaccessibility of mercury in contaminated soils and potential health risk to the kidneys and neurodevelopment of children in Taiwan - Ying-Lin Wang; Ming-Chien Mark Tsou; Li-Chi Lai; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Geochemistry and Health, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Large-scale assessment of exposure to legacy and emerging per- and polyfluoroalkyl substances in China's shorebirds - Jiachen Sun; Yachang Cheng; Zitan Song; Shisheng Ma; Lingling Xing; Kai Wang; Chenjing Huang; Donglai Li; Jiansong Chu; Yang Liu (Environmental Research, 2023)

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Sodium alginate reinforced polyacrylamide/xanthan gum double network ionic hydrogels for stress sensing and self-powered wearable device applications - Tuo Li; Huige Wei; Yingying Zhang; Tong Wan; Dapeng Cui; Shixiang Zhao; Teng Zhang; Yanxiu Ji; Hassan Algadi; Zhanhu Guo; Liqiang Chu; Bowen Cheng (Carbohydrate Polymers, 2023)

Kinetics of PCDD/Fs from feed to cow milk and its implications for food safety - Yanfen Hao; Chu Wang; Pu Wang; Jie Cheng; Hao Xian; Mei Liu; Zengwei Li; Jie Ma; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Xiaoou Su; et al. (Science of The Total Environment, 2023)

Construction of Z scheme S-g-C3N4/Bi5O7I photocatalysts for enhanced photocatalytic removal of Hg0 and carrier separation - Zhanwei Qiao; Weiqun Chu; Hao Zhou; Cheng Peng; Zhenzhen Guan; Jiang Wu; Sorachon Yoriya; Ping He; Hai Zhang; Yongfeng Qi (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

A unique suit of Wuchiapingian marine red beds in central China representing a specific paleogeography and paleoclimate association - Cheng Cheng; Zi'an Shan; Mingyu Shan; Zhonglai Zhou; Bingyan Ren; Yike Chu; Shuangying Li; Dan Wang; Hongzuo Wang; Xujie Shu; Peng Qian (Marine and Petroleum Geology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Development of p-type zinc oxide nanorods on zirconium-based metallic glass nanotube arrays by facile hydrothermal method for gas sensing applications - Shrisha; Chang-Mou Wu; Kebena Gebeyehu Motora; Guan-Ying Chen; Jinn P. Chu; Yichia Cheng; Hsiao-Hsuan Hsu (Chemical Engineering Journal, 2023)

Continuous cropping of cut chrysanthemum reduces rhizospheric soil bacterial community diversity and co-occurrence network complexity - Jun Li; Xiaoyu Cheng; Guixin Chu; Baowei Hu; Rui Tao (Applied Soil Ecology, 2023)

Shallow water bathymetry based on a back propagation neural network and ensemble learning using multispectral satellite imagery - Sensen Chu; Liang Cheng; Jian Cheng; Xuedong Zhang; Jie Zhang; Jiabing Chen; Jinming Liu (Acta Oceanologica Sinica, 2023)

Release characteristics of hydrochar-derived dissolved organic matter: Effects of hydrothermal temperature and environmental conditions - Rongting Ji; Yue Zhou; Jinbang Cai; Kejian Chu; Yuan Zeng; Hu Cheng (Chemosphere, 2023)

Physcion, a novel anthraquinone derivative against Chlamydia psittaci infection - Xinyi Liu; Huilong Hu; Jiaqi Liu; Jiaqi Chen; Jun Chu; He Cheng (Veterinary Microbiology, 2023)

pUGTdb: A comprehensive database of plant UDP-dependent glycosyltransferases - Yuqian Liu; Qian Wang; Xiaonan Liu; Jian Cheng; Lei Zhang; Huanyu Chu; Ruoyu Wang; Haoran Li; Hong Chang; Nida Ahmed; Zhonghua Wang; Xiaoping Liao; et al. (Molecular Plant, 2023)

Change of turbidity maximum in Yangtze Estuary after construction of the Three Gorges Dam - Leihua Zhao; Pei Xin; Haifeng Cheng; Ao Chu (Continental Shelf Research, 2023)

Effects of salinity on anoxic–oxic system performance, microbial community dynamics and co-occurrence network during treating wastewater - Hui Chen; Yangyang Wang; Zhu Chen; Zhiqiang Wu; Xueyan Chu; Shengqiang Qing; Longqi Xu; Kang Yang; Qingyuanhao Meng; Haina Cheng; Wenhao Zhan; Yuguang Wang; et al. (Chemical Engineering Journal, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Nocardia seriolae cell wall lipids: An effective protective mechanism in resistance and virulence - Sandra Celenia Nazareth; Shreesha Rao; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Piscine nocardiosis, caused by Nocardia seriolae , is a refractory granulomatous disease in South‐East Asian aquaculture. This study investigates the virulence of nocardial lipids essential for pathogenesis among Actinomycetes. Petroleum ether (PE) was used to selectively delipidate two groups of N. seriolae , namely, live cell (LC) and killed cell (KC); resulting in delipidated live cell (DLC) and delipidated killed cell (DKC), respectively. Changes post‐delipidation on genus characteristics, such as loss in acid‐fast nature and resistance to lysozyme were observed. Transmission electron microscopy revealed notable changes in the lipid layer. Additionally, Lates calcarifer , Asian seabass intraperitoneally injected with LC and DLC had mortality rates of 90% and 50%, respectively, with the latter exhibiting a delay in mortality. Reverse‐transcription quantitative PCR (RT‐qPCR) analysis of host cytokines from the spleen and head kidney showed delipidation contributed to the induction of an immune response with increased transcriptional levels of interferon‐γ ( ifn‐γ ). Histopathological samples collected on day 7 post‐inoculation displayed a varied granulomatous response between the treatment groups and scored for pathological changes. These findings affirm that the virulence of the lipids remains independent of the living state of the cell, significantly altering the immune and granulomatous responses in L. calcarifer to N. seriolae.

Comparison of Six Empirical Methods for Multispectral Satellite-derived Bathymetry - Sensen Chu; Liang Cheng; Jian Cheng; Xuedong Zhang; Jinming Liu (Marine Geodesy, 2023)

Development of AIoT System for facility asparagus cultivation - Cheng-Ying Chou; Shan-Cheng Chang; Zi-Ping Zhong; Ming-Chi Guo; Ming-Hsien Hsieh; Jui-Chu Peng; Ling-Chieh Tai; Ping-Liang Chung; Jen-Cheng Wang; Joe-Air Jiang (Computers and Electronics in Agriculture, 2023)

Biochar application can mitigate NH3 volatilization in acidic forest and upland soils but stimulates gaseous N losses in flooded acidic paddy soil - Cheng Chu; Shenyan Dai; Lei Meng; Zucong Cai; Jinbo Zhang; Christoph Müller (Science of The Total Environment, 2023)

Energy-efficient single-machine scheduling with release dates under time-of-use electricity tariffs - Peng Wu; Nan Li; Junheng Cheng; Chengbin Chu (Journal of Cleaner Production, 2023)

Establishment and characterization of immortalized human vocal fold fibroblast cell lines - Yinying Chu; Yi Fang; Haitao Wu; Lei Cheng; Jian Chen (Biotechnology Letters, 2023)

Plastic film-mulched ridges and straw-mulched furrows increase soil carbon sequestration and net ecosystem economic benefit in a wheat-maize rotation - Xiaoqi Luo; Cheng Li; Nanping Lin; Naijiang Wang; Xiaosheng Chu; Hao Feng; Haixin Chen (Agriculture, Ecosystems & Environment, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

Heavy metal(loid)s in agricultural soil from main grain production regions of China: Bioaccessibility and health risks to humans - Cheng-Chen Wang; Qiao-Chu Zhang; Shao-Guo Kang; Meng-Ying Li; Meng-Yan Zhang; Wu-Mei Xu; Ping Xiang; Lena Q. Ma (Science of The Total Environment, 2023)

Modeling the leeway drift characteristics of persons-in-water at a sea-area scale in the seas of China - Jie Wu; Liang Cheng; Sensen Chu (Ocean Engineering, 2023)

Semi-quantitative evaluation of levees risk within the context of hydrology uncertainty - Chia-Chu Chu; Ho-Ting Su; Cheng Wei; Gene Jiing-Yun You (Journal of Hydrology, 2023)

6His-tatritin promotes antimicrobial defense via regulating immune ability and intestinal microbial community in grass carp (Ctenopharyngodon idella) - Wei-Feng Wang; Chu-Xing Cheng; Hong Liu; Xiu-Li Chen; Huan-Ling Wang (Fish & Shellfish Immunology, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Distribution and toxicity of submicron plastic particles in mice - Tsung-Yen Tsou; Sheng-Han Lee; Tzu-Hsuan Kuo; Chu-Chun Chien; Hsin-Chang Chen; Tsun-Jen Cheng (Environmental Toxicology and Pharmacology, 2023)

An injectable, self-healing composite hydrogel with enhanced near-infrared photo-antibacterial therapeutic effects for accelerated wound healing - Jiameng Wang; Hao Cheng; Weiyi Chen; Peide Han; Xiaohong Yao; Bin Tang; Wangping Duan; Pengcui Li; Xiaochun Wei; Paul K. Chu; Xiangyu Zhang (Chemical Engineering Journal, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Cationic molecular probes based on aggregation-induced emission for fluorescent sensing and super-resolution imaging of insulin fibrosis - Li-Jun Mei; Cheng Fan; Chu-Ran Xu; Qi Yu; Chong Li; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2023)

Integrating multiple redox-active sites and universal electrode-active features into covalent triazine frameworks for organic alkali metal-ion batteries - Juan Chu; Linqi Cheng; Lan Chen; Heng-guo Wang; Fengchao Cui; Guangshan Zhu (Chemical Engineering Journal, 2023)

Mixotrophic culture of bait microalgae for biomass and nutrients accumulation and their synergistic carbon metabolism - Yahui Bo; Ruirui Chu; Danni Sun; Xiangyuan Deng; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Comparison of pulsed-field gel electrophoresis and a novel amplified intergenic locus polymorphism method for molecular typing of Campylobacter jejuni - Jin-Hong Liu; Cheng-Lu Lan; Ge-Feng Yao; Nian-Qing Kong; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Archives of Microbiology, 2023)

Rapid antidepressant-like effects of muscarinic receptor antagonists require BDNF-dependent signaling in the ventrolateral periaqueductal gray - Hung-Wei Kan; Wei-Hao Peng; Cheng-Chun Wu; Deng-Wu Wang; Ming Tatt Lee; Yung-Kuo Lee; Tian-Huei Chu; Yu-Cheng Ho (Psychopharmacology, 2022)

New time-differenced carrier phase approach to GNSS/INS integration - Yi Mao; Rui Sun; Junhui Wang; Qi Cheng; Loo Chu Kiong; Washington Yotto Ochieng (GPS Solutions, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Groundwater vulnerability assessment of shallow aquifer in the South Texas sand sheet using a GIS-based DRASTIC model - Syed Istiyak Ahmed; Chu-Lin Cheng; Juan Gonzalez; James J. Kang; Jungseok Ho; Leslie Soto-Sanchez (Modeling Earth Systems and Environment, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Influence of accelerometer type on uncertainties in recorded ground motions and seismic damage assessment - Wenjie Liao; Yifan Fei; Farid Ghahari; Wenyang Zhang; Peng-Yu Chen; Asli Kurtulus; Chu-Han Yen; Qingle Cheng; Xinzheng Lu; Ertugrul Taciroglu (Bulletin of Earthquake Engineering, 2022)

Effect of starvation and refeeding on reactive oxygen species, autophagy and oxidative stress in Chinese perch ( Siniperca chuatsi ) muscle growth - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xin Zhu; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2022)
In skeletal muscle, autophagy regulates the development and growth of muscle fibres and maintains the normal muscle metabolism. Under starvation and refeeding conditions, the effect of reactive oxygen species (ROS) levels on skeletal muscle autophagy is still unclear, although the excessive accumulation of ROS has been shown to increase autophagy in cells. The purpose of this study was to explore the effects of starvation and diet after starvation on the autophagy of adult Chinese perch muscle, and to determine the level of ROS in the muscle. We performed zero (Normal control), three and seven starvation treatments on adult Chinese perch, and returned to normal feeding for 3 days after starvation for 7 days. In the muscles of the adult Chinese perch muscle after 3 days of starvation, the autophagy marker protein LC3 and the number of autophagosomes remained basically the same as in the normal feeding situation. However, on starvation for 7 days, the mitochondrial autophagy was sensitive and the number of autophagosomes increased, but the antioxidant‐related molecules (malondialdehyde, catalase, glutathione S‐transferase, glutathione and anti‐superoxide anion) decreased and the accumulation of ROS was obvious. In addition, the extended starvation time also increased the level of LC3 protein. However, by refeeding after starvation this nutritional stress resulted in a decrease in ROS levels and a partial restoration of antioxidant enzyme activity. Our data show that in the adult Chinese perch muscle, starvation could reduce the antioxidant activity through the accumulation of ROS, and that the number of autophagosomes continues to increase. Refeeding after starvation could effectively compensate for the level of ROS, and restore the mRNA abundance of antioxidant genes and the activity of antioxidant enzymes to reduce autophagy and improve feed efficiency. Further research should optimize starvation conditions to reduce autophagy in muscles and maintain normal muscle metabolism.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The role of lncRNA OIP5-AS1 in cancer development and progression - Cheng Zheng; Man Chu; Qiuli Chen; Cheng Chen; Zhi-Wei Wang; Xiao Chen (Apoptosis, 2022)

Framework for Automatic Coral Reef Extraction Using Sentinel-2 Image Time Series - Qizhi Zhuang; Jian Zhang; Liang Cheng; Hui Chen; Yanruo Song; Song Chen; Sensen Chu; Shengkun Dongye; Manchun Li (Marine Geodesy, 2022)

First report of acanthocephalan parasite, Longicollum pagrosomi Yamaguti, 1935 in cultured red snapper ( Lutjanus erythropterus ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
For the first time, Longicollum pagrosomi Yamaguti, 1935, an acanthocephalan parasite, has been characterized with morphological, histopathological and molecular detail in farmed red snapper ( Lutjanus erythropterus ) in Taiwan. The diseased fish showed clinical signs of anorexia, emaciation and were gasping for air at the water's surface. Gross examination revealed extensive necrosis in the intestine and even penetration at the site of parasitic attachment, resulting in a large number of parasites being lodged in the peritoneal cavity, surrounded by black hyperplastic connective tissue. The parasites collected from the intestine were studied using optical microscopy, histopathology, scanning electron microscopy (SEM) and molecular phylogenetic analysis. They were creamy white in colour, and were separated into their proboscis, neck and metasoma (trunk) under optical microscopy. Histopathological examination revealed ovarian balls (floating ovaries) inside the ligament sac and eggs within the egg sorting apparatus. The SEM images revealed that the proboscis had 11–14 longitudinal rows with 9–12 recurrent, backward‐facing, organized hooks. In the 18S and 28S phylogenetic tree, sequences of the specimens were identical to those of other Longicollum pagrosomi , in addition to the morphological features. Thus, we confirmed that the parasites belonged to Longicollum pagrosomi in this study.

Bone Marrow Mesenchymal Stem Cells Exert Protective Effects After Ischemic Stroke Through Upregulation of Glutathione - Xiao-Yan Lan; Zheng-Wu Sun; Gui-Lian Xu; Cheng-Yan Chu; Hua-Min Qin; Shen Li; Xin Geng; Peng Gao; Johannes Boltze; Shen Li (Stem Cell Reviews and Reports, 2022)

LncRNA Riken Attenuated Sevoflurane-Induced Neuroinflammation by Regulating the MicroRNA-101a/MKP-1/JNK Pathway - Qi Hou; Shuai Li; Bo Zhang; Huaqing Chu; Cheng Ni; Xuejie Fei; Hui Zheng (Neurotoxicity Research, 2022)

Hybrid Anticancer Peptides DN1 and DN4 Exert Selective Cytotoxicity Against Hepatocellular Carcinoma Cells by Inducing Both Intrinsic and Extrinsic Apoptotic Pathways - Chu Xin Ng; Cheng Foh Le; Yin Sim Tor; Sau Har Lee (International Journal of Peptide Research and Therapeutics, 2021)

A novel regQTL-SNP and the risk of lung cancer: a multi-dimensional study - Yuhui Yu; Liping Mao; Zhounan Cheng; Xiaoqi Zhu; Jiahua Cui; Xiaoyu Fu; Jingwen Cheng; Yan Zhou; Anni Qiu; Yang Dong; Xun Zhuang; Yihua Lu; et al. (Archives of Toxicology, 2021)

Genotype and virulence gene analyses of Bacillus cereus group clinical isolates from the Chinese softshell turtle ( Pelodiscus sinensis ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Sayuj Poudyal; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2021)
Chinese softshell turtles ( Pelodiscus sinensis ) (CST) are susceptible to infections by bacteria belonging to the Bacillus cereus group (Bcg). Bcg includes several closely related species, two of which, B . cereus and B . thuringiensis , are pathogens of aquatic animals or insects. In the present study, we collected 57 Bcg isolates from diseased CST from 2016 to 2019 in Kaohsiung and Pingtung, where most CST farms are located in Taiwan. All isolates were divided into four genotypes with two restriction enzymes, Sma I and Not I, by pulsed‐field gel electrophoresis and enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC‐PCR). Representative isolates from each genotype were subjected to phylogenetic tree analysis using 16S rDNA and pyruvate carboxylase genes as phylogenetic markers, and these CST isolates appeared in different clades. PCR was performed targeting six selected virulence genes, four of which were detected in CST isolates, including cytotoxin K (1/57), hblC of the haemolysin BL complex (46/57), nheA of the non‐haemolytic enterotoxin complex (52/57) and enterotoxin FM (57/57), whereas cereulide synthetase and cereulide peptide synthase‐like genes were not detected in any isolates.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

A New Direct Shear Apparatus for Rock Joints Specialized in Cyclic Loading - Zhen Cui; Qian Sheng; Mao-chu Zhang; Jun-feng Cao; Xian-cheng Mei; Qing-zi Luo (Rock Mechanics and Rock Engineering, 2021)

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

A simple Monte Carlo method for estimating the chance of a cyclone impact - Xiaoliang Xie; Bingqi Xie; Jiaqi Cheng; Qi Chu; Thomas Dooling (Natural Hazards, 2021)

Lesions of abdominal connectives reveal a conserved organization of the calling song central pattern generator (CPG) network in different cricket species - Chu-Cheng Lin; Berthold Hedwig (Journal of Comparative Physiology A, 2021)
Although crickets move their front wings for sound production, the abdominal ganglia house the network of the singing central pattern generator. We compared the effects of specific lesions to the connectives of the abdominal ganglion chain on calling song activity in four different species of crickets, generating very different pulse patterns in their calling songs. In all species, singing activity was abolished after the connectives between the metathoracic ganglion complex and the first abdominal ganglion A3 were severed. The song structure was lost and males generated only single sound pulses when connectives between A3 and A4 were cut. Severing connectives between A4 and A5 had no effect in the trilling species, it led to an extension of chirps in a chirping species and to a loss of the phrase structure in two Teleogryllus species. Cutting the connectives between A5 and A6 caused no or minor changes in singing activity. In spite of the species-specific pulse patterns of calling songs, our data indicate a conserved organisation of the calling song motor pattern generating network. The generation of pulses is controlled by ganglia A3 and A4 while A4 and A5 provide the timing information for the chirp and/or phrase structure of the song.

Establishment and characterization of 38 novel patient-derived primary cancer cell lines using multi-region sampling revealing intra-tumor heterogeneity of gallbladder carcinoma - Feiling Feng; Qingbao Cheng; Bin Li; Chen Liu; Huizhen Wang; Bin Li; Xiaoya Xu; Yong Yu; Zishuo Chen; Xiaobing Wu; Hua Dong; Kaijian Chu; et al. (Human Cell, 2021)
Gallbladder carcinoma (GBC) is a lethal biliary tract malignant neoplasm. Patient-derived primary cancer cell lines (PDPCs) are appropriate models to explore biological characteristics and potential therapeutics; however, there is a lack of PDPCs in GBC. In this study, we aimed to establish and characterize the GBC PDPCs, and further investigated the intra-tumor heterogeneity (ITH). Multi-region sampling (3–9 regions) of the operable tumor tissue samples was used to establish PDPCs. Short tandem repeat genotyping for cell authentication and karyotyping was performed, followed by whole-exome sequencing and RNA sequencing to assess the ITH at the genetic and transcriptional levels, respectively. Thirty-eight PDPCs were successfully established from seven GBC patients and characterized. ITH was observed with a median of 38.3% mutations being heterogeneous (range, 26.6–59.4%) across all patients. Similar with other tumor types, TP53 mutations were always truncal. In addition, there were three genes, KMT2C , CDKN2A , and ARID1A , with truncal mutations in at least two patients. A median of 370 differentially expressed genes (DEGs) was identified per patient. Distinct expression patterns were observed between major histocompatibility complex (MHC) class I and II genes. We found the expression of MHC class II genes in the PDPC samples was closely regulated by CIITA , while that of MHC class I genes were not correlated with CIITA expression. The PDPCs established from GBC patients can serve as novel in vitro models to identify the ITH, which may pave a crucial molecular foundation for enhanced understanding of tumorigenesis and progression.

Selection and optimum fertilization of Betula platyphylla hybrid clones for growth - Shuyuan Song; Siqi Cheng; Zhen Jia; Minghui Li; Jiabao Ji; Yifan Yang; Chu Wang; Chenrui Gu; Qibin Yu; Yuhui Weng; Guifeng Liu (Trees, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

A Visual Analysis Approach to Understand and Explore Quality Problems of AIS Data - Wei He; Jinyu Lei; Xiumin Chu; Shuo Xie; Cheng Zhong; Zhixiong Li (Journal of Marine Science and Engineering, 2021)
Low quality automatic identification system (AIS) data often mislead analysts to a misunderstanding of ship behavior analysis and to making incorrect navigation risk assessments. It is therefore necessary to accurately understand and judge the quality problems in AIS data before a further analysis of ship behavior. Outliers were filtered in the existing methods of AIS quality analysis based only on mathematical models where AIS data related quality problems are not utilized and there is a lack of visual exploration. Thus, the human brain’s ability cannot be fully utilized to think visually and for reasoning. In this regard, a visual analytics (VA) approach called AIS Data Quality visualization (ADQvis) was designed and implemented here to support evaluations and explorations of AIS data quality. The system interface is overviewed and then the visualization model and corresponding human-computer interaction method are described in detail. Finally, case studies were carried out to demonstrate the effectiveness of our visual analytics approach for AIS quality problems.

Design of the Blade under Low Flow Velocity for Horizontal Axis Tidal Current Turbine - Jun-Hua Chen; Xian-Cheng Wang; Hao Li; Chu-Hua Jiang; Ling-Jie Bao (Journal of Marine Science and Engineering, 2020)
The blade is the key component for energy capture in horizontal axis tidal current turbine, and the blade’s design is directly related to the efficiency of the power generation device. The seawater flow velocity is a crucial parameter for blade design. Since the seawater velocity changes constantly, it is extremely important to determine the design velocity of the blade. This article proposes a calculation method for the design velocity of the blade so that the designed blade can achieve better energy collection efficiency under a variable flow velocity. This study performed the following investigations: (1) The author tested and analyzed the seawater velocity variation at the experimental site, determining the designed flow velocity via calculations; (2) The author combined the blade element momentum and Wilson’s optimization design method using the MATLAB software to calculate the blade shape parameters and predict the performance under a number of different flow velocity forecasts; (3) When testing the device under sea conditions, the experimental results showed that the performance capture devices and digital projections are basically the same, which verifies the validity and effectiveness of the design method.

Numerical Analysis of Vertical Breakwater Stability under Extreme Waves - Meng-Syue Li; Cheng-Jung Hsu; Hung-Chu Hsu; Li-Hung Tsai (Journal of Marine Science and Engineering, 2020)
The purpose of this study is to perform a numerical simulation of caisson breakwater stability concerning the effect of wave overtopping under extreme waves. A numerical model, which solves two-dimensional Reynolds-averaged Navier–Stokes equations with the k−ε turbulence closure and uses the volume of fluid method for surface capturing, is validated with the laboratory observations. The numerical model is shown to accurately predict the measured free-surface profiles and the wave pressures around a caisson breakwater. Considering the dynamic loading on caisson breakwaters during overtopping waves, not only landward force and lift force but also the seaward force are calculated. Model results suggest that the forces induced by the wave overtopping on the back side of vertical breakwater and the phase lag of surface elevations have to be considered for calculating the breakwater stability. The numerical results also show that the failure of sliding is more dangerous than the failure of overturning in the vertical breakwater. Under extreme waves with more than 100 year return period, the caisson breakwater is sliding unstable, whereas it is safe in overturning stability. The influence of wave overtopping on the stability analysis is dominated by the force on the rear side of the caisson and the phase difference on the two ends of caisson. For the case of extreme conditions, if the impulse force happens at the moment of the minimum of load in the rear side, the safety factor might decrease significantly and the failure of sliding might cause breakwater damage. This paper demonstrates the potential stability failure of coastal structures under extreme sea states and provides adapted formulations of safety factors in dynamic form to involve the influence of overtopping waves.

Clinical Characteristics and Outcomes of Candidemia Caused by Meyerozyma guilliermondii Complex in Cancer Patients Undergoing Surgery - Jingjing Chen; Sufei Tian; Fushun Li; Guoquan Sun; Ke Yun; Shitong Cheng; Yunzhuo Chu (Mycopathologia, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Anxiety is associated with increased risk for atrial cardiopathy - Zhaolu Wang; Huiyuan Qin; Guilin Chen; Yan Dai; Yingyuan Cai; Xi Cheng; Yun Qian; Ming Chu; Xiaowei Lu (Acta Neurologica Belgica, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

MiRNAs-Modulation of Nrf2 Signaling Networks in Regulation Oxidative Stress of Chinese Perch Skeletal Muscle After Fasting Treatment - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xinhong Guo; Wuying Chu; Jianshe Zhang; Xuanming Liu (Marine Biotechnology, 2020)

Real-Time Position and Attitude Estimation for Homing and Docking of an Autonomous Underwater Vehicle Based on Bionic Polarized Optical Guidance - Haoyuan Cheng; Jinkui Chu; Ran Zhang; Xinyuan Gui; Lianbiao Tian (Journal of Ocean University of China, 2020)

Phylogenetic analysis of the whole genome sequence of a dog lineage rabies virus detected from cattle in eastern China, 2019 - Kaihui Cheng; Huimeng Chu; Yachu Ren; Xiaoli Xie; Zhijun Yu; Hongjun Yang (Brazilian Journal of Microbiology, 2020)

Clinical and Genetic Characterization of Autosomal Recessive Spinocerebellar Ataxia Type 16 (SCAR16) in Taiwan - Hsu-Huai Chiu; Cheng-Tsung Hsaio; Yu-Shuen Tsai; Yi-Chu Liao; Yi-Chung Lee; Bing-Wen Soong (The Cerebellum, 2020)

Underwater polarization patterns considering single Rayleigh scattering of water molecules - Haoyuan Cheng; Jinkui Chu; Ran Zhang; Lianbiao Tian; Xinyuan Gui (International Journal of Remote Sensing, 2020)

Genotypic diversity, and molecular and pathogenic characterization of Photobacterium damselae subsp. piscicida isolated from different fish species in Taiwan - Trung Hieu Pham; Ta‐Chih Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2020)
Photobacteriosis, caused by Photobacterium damselae subsp. piscicida ( Phdp ), is a serious disease in marine fish species worldwide. To date, the epidemiological characterization of this pathogen in Taiwan remains limited. In this study, we collected 39 Phdp isolates obtained from different farmed fish for phenotypic and genotypic analysis. Phenotype bioassays using API‐20E and API‐20NE systems showed that the Phdp is a homogeneous group. However, genotyping using the pulsed‐field gel electrophoresis (PFGE) technique revealed genetic variability among Phdp isolates when 13 and 11 different PFGE band patterns were obtained with SmaI and NotI as restriction enzymes, respectively. Phylogenetic analysis using 16S rDNA and the Fur gene clustered Taiwanese isolates and other species of P. damselae in the same clade. In contrast, the ToxR phylogenetic tree, a powerful discriminatory marker, separated the two subspecies. Furthermore, the virulence‐associated genes, AIP56, P55, PDP_0080, Sod and Irp1, were detected from all isolates. Virulence testing with nine representative isolates in cobia ( Rachycentron canadum ) and Asian sea bass ( Lates calcarifer ) showed that some were highly pathogenic with 80%–100% mortality rates. This study provides epidemiological data of Phdp infections in farmed fish in Taiwan, which is necessary to develop comprehensive prevention and control strategies for the disease.

Non-uniform Distributions of Gas Pressure and Coal Permeability in Coalbed Methane Reservoirs Induced by the Loess Plateau Geomorphology: A Case Study in Ordos Basin, China - Qingquan Liu; Peng Chu; Congmeng Hao; Yuanping Cheng; Haifeng Wang; Liang Wang (Natural Resources Research, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Nr1d1 affects autophagy in the skeletal muscles of juvenile Nile tilapia by regulating the rhythmic expression of autophagy-related genes - Ping Wu; Jia Cheng; Lin Chen; Jing Xiang; Yaxiong Pan; Yongzhan Zhang; Tao Zheng; Naiyuan Liu; Wuying Chu; Jianshe Zhang (Fish Physiology and Biochemistry, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Crocin attenuates isoprenaline-induced myocardial fibrosis by targeting TLR4/NF-κB signaling: connecting oxidative stress, inflammation, and apoptosis - Weiyue Jin; Yuanyuan Zhang; Yurun Xue; Xue Han; Xuan Zhang; Zhihong Ma; Shijiang Sun; Xi Chu; Jie Cheng; Shengjiang Guan; Ziliang Li; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Evaluation of Different Modulation Transfer Function Measurement Based on Different Edge Spread Function Calculations - Yu-Wei Tsai; Chien-Hau Chu; Wei-Hung Shih; Shih-Chun Jin; Jyh-Cheng Chen; Kai-Chieh Liang (Journal of Medical and Biological Engineering, 2019)

Construction of a Lactobacillus plantarum Strain Expressing the Capsid Protein of Porcine Circovirus Type 2d (PCV2d) as an Oral Vaccine - Yi-Han Tseng; Cheng-Chu Hsieh; Tsun-Yung Kuo; Je-Ruei Liu; Ting-Yu Hsu; Shu-Chen Hsieh (Indian Journal of Microbiology, 2019)

Dynamic modifications of biomacromolecules: mechanism and chemical interventions - Chu Wang; Peng Zou; Caiguang Yang; Lei Liu; Liang Cheng; Xiaopeng He; Liang Zhang; Yan Zhang; Hualiang Jiang; Peng R. Chen (Science China Life Sciences, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Transcriptome and key gene expression related to carbon metabolism and fatty acid synthesis of Chlorella vulgaris under a nitrogen starvation and phosphorus repletion regime - Feifei Chu; Jun Cheng; Xiangdong Zhang; Qing Ye; Shutong Chen; Junhu Zhou; Kefa Cen (Journal of Applied Phycology, 2019)

The effects of negative air ions on cognitive function: an event-related potential (ERP) study - Chien-Heng Chu; Su-Ru Chen; Chih-Han Wu; Yung-Chao Cheng; Yu-Min Cho; Yu-Kai Chang (International Journal of Biometeorology, 2019)

Pathological Alterations of Tau in Alzheimer’s Disease and 3xTg-AD Mouse Brains - Longfei Li; Yanli Jiang; Wen Hu; Yunn Chyn Tung; Chunling Dai; Dandan Chu; Cheng-Xin Gong; Khalid Iqbal; Fei Liu (Molecular Neurobiology, 2019)

Prevalence of mycotoxins in feed and feed ingredients between 2015 and 2017 in Taiwan - Ching-Kuo Yang; Yeong-Hsiang Cheng; Wan-Ting Tsai; Rou-Wan Liao; Chia-Sheng Chang; Wan-Chu Chien; Jia-Cin Jhang; Yu-Hsiang Yu (Environmental Science and Pollution Research, 2019)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

An End-to-end System for Automatic Characterization of Iba1 Immunopositive Microglia in Whole Slide Imaging - Alexander D. Kyriazis; Shahriar Noroozizadeh; Amir Refaee; Woongcheol Choi; Lap-Tak Chu; Asma Bashir; Wai Hang Cheng; Rachel Zhao; Dhananjay R. Namjoshi; Septimiu E. Salcudean; Cheryl L. Wellington; Guy Nir (Neuroinformatics, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

Antiproliferative activity of ursolic acid/glycyrrhetinic acid-uracil/thymine hybrids - Li Sun; Xiang-Wu Chu; Chun-mei Liu; Li-Xin Sheng; Zhuan-Xin Chen; Ke-Guang Cheng (Medicinal Chemistry Research, 2019)

Distribution of mercury and methylmercury in surface water and surface sediment of river, irrigation canal, reservoir, and wetland in Taiwan - Ying-Lin Wang; Meng-Der Fang; Ling-Chu Chien; Chu-Ching Lin; Hsing-Cheng Hsi (Environmental Science and Pollution Research, 2019)

Comparative Analysis of Expression Profiles of Reg Signaling Pathways-Related Genes Between AHF and HCC - Gaiping Wang; Liya Cheng; Meng Chen; Congcong Zhao; Mingxin Gao; Tiantian Huang; Peipei Chu; Cunshuan Xu (Biochemical Genetics, 2019)

Overexpression of an ABA-dependent grapevine bZIP transcription factor, VvABF2, enhances osmotic stress in Arabidopsis - Jinyi Liu; Jinjin Chu; Chuangju Ma; Yueting Jiang; Yuanchun Ma; Jinsong Xiong; Zong-Ming Cheng (Plant Cell Reports, 2019)

Polymer translocation through a hairy channel mimicking the inner plug of a nuclear pore complex - Chibin Zhang; Zhiwei Cheng; Xiaohui Lin; Wenquan Chu (European Biophysics Journal, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

The effects of particulate matters on allergic rhinitis in Nanjing, China - Haiyan Chu; Junyi Xin; Qi Yuan; Meilin Wang; Lei Cheng; Zhengdong Zhang; Meiping Lu (Environmental Science and Pollution Research, 2019)

Sema4D expression and secretion are increased by HIF-1α and inhibit osteogenesis in bone metastases of lung cancer - Wu-gui Chen; Jing Sun; Wei-wei Shen; Si-zhen Yang; Ying Zhang; Xu Hu; Hao Qiu; Shang-cheng Xu; Tong-wei Chu (Clinical & Experimental Metastasis, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

A quantum theory investigation on atmospheric oxidation mechanisms of acrylic acid by OH radical and its implication for atmospheric chemistry - Han Chu; Wenzhong Wu; Youxiang Shao; Yizhen Tang; Yunju Zhang; Yinfang Cheng; Fang Chen; Jiangyan Liu; Jingyu Sun (Environmental Science and Pollution Research, 2018)

Surface Water Control for Mining Thick, Relatively Shallow Coal Seams in the Loess Area of Western China - Ge Zhu; Xiong Wu; Shan Yu; Cheng Qian; Yanyan Dong; Chaojun Zhang; Chu Wu (Mine Water and the Environment, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

A Neuron-Specific Gene Therapy Relieves Motor Deficits in Pompe Disease Mice - Ni-Chung Lee; Wuh-Liang Hwu; Shin-Ichi Muramatsu; Darin J. Falk; Barry J. Byrne; Chia-Hao Cheng; Nien-Chu Shih; Kai-Ling Chang; Li-Kai Tsai; Yin-Hsiu Chien (Molecular Neurobiology, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

GbABR1 is associated with Verticillium wilt resistance in cotton - Yujia Liu; Xin Liu; Lu Long; Weina Wang; Quan Sun; Bo Li; Chenxiao Wang; Jieru Cheng; Yuanyuan Zhang; Yuanhui Xie; Lingling Xu; Runkuan Qin; et al. (Biologia, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

LiDAR-based three-dimensional street landscape indices for urban habitability - Liang Cheng; Song Chen; Sensen Chu; Shuyi Li; Yi Yuan; Yu Wang; Manchun Li (Earth Science Informatics, 2017)

Using major nutrient concentrations to derive vertical movement of water masses in the coastal region of eastern Taiwan - Su-Cheng Pai; Sen Jan; Tung-Yuan Ho; Jin-Yuan Liu; Ken-Sheng Chu; Wen-Huei Lee; Cheng-Yun Wang; Ping-Yi Huang; Hung-Yu Hsu; Yiing-Jang Yang (Journal of Oceanography, 2017)

Using leaf area index (LAI) to assess vegetation response to drought in Yunnan province of China - Kwangchol Kim; Ming-cheng Wang; Sailesh Ranjitkar; Su-hong Liu; Jian-chu Xu; Robert J. Zomer (Journal of Mountain Science, 2017)

Research progress on the autonomous flowering time pathway in Arabidopsis - Jing-Zhi Cheng; Yu-Ping Zhou; Tian-Xiao Lv; Chu-Ping Xie; Chang-En Tian (Physiology and Molecular Biology of Plants, 2017)

A BRCA1-Dependent DNA Damage Response in the Regenerating Adult Peripheral Nerve Milieu - Anand Krishnan; Kaylynn Purdy; Ambika Chandrasekhar; Jose Martinez; Chu Cheng; Douglas W. Zochodne (Molecular Neurobiology, 2017)

IRF9-Stat2 Fusion Protein as an Innate Immune Inducer to Activate Mx and Interferon-Stimulated Gene Expression in Zebrafish Larvae - Chang-Jen Huang; Chih-Ming Chou; Huang-Wei Lien; Cheng-Ying Chu; Jhih-Yun Ho; Yimin Wu; Chia-Hsiung Cheng (Marine Biotechnology, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Molecular characterisation and functional analysis of a cytochrome P450 gene in cotton - Kexue Zhou; Lu Long; Quan Sun; Weina Wang; Wei Gao; Zongyan Chu; Chaowei Cai; Jianchuan Mo; Jieru Cheng; Xiangrui Zhang; Yujia Liu; Xiongming Du; et al. (Biologia, 2017)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

Preliminary Measurements of Binaural Masking-Level Difference When Using Hearing Aids for Sensorineural Hearing Loss - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Wen-Ying Yeh; Chih-Hung Wang; Woei-Chyn Chu (Journal of Medical and Biological Engineering, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Detection of Seismic Bedrock Using Radial Receiver Function - Cheng-Feng Wu; Huey-Chu Huang (Pure and Applied Geophysics, 2016)

Forelimb contractures and abnormal tendon collagen fibrillogenesis in fibulin-4 null mice - Dessislava Z. Markova; Te-Cheng Pan; Rui-Zhu Zhang; Guiyun Zhang; Takako Sasaki; Machiko Arita; David E. Birk; Mon-Li Chu (Cell and Tissue Research, 2016)

Roseomonas chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from activated sludge - Cui-Wei Chu; Qing Chen; Cheng-Hong Wang; Hong-Mei Wang; Zhong-Guan Sun; Qin He; Jian He; Jin-Gang Gu (Antonie van Leeuwenhoek, 2016)

Effect of diversity on biomass across grasslands on the Mongolian Plateau: contrasting effects between plants and soil nematodes - Dima Chen; Junhui Cheng; Pengfei Chu; Jia Mi; Shuijin Hu; Yichun Xie; Indree Tuvshintogtokh; Yongfei Bai (Journal of Biogeography, 2016)
Aim To assess how the diversity of above‐ and below‐ground organisms changes along environmental gradients at the regional scale and whether the effects of diversity changes on biomass are similar for above‐ and below‐ground organisms. Location Semi‐arid grasslands of the Mongolian Plateau. Methods We investigated diversity (α‐, β‐ and γ‐) and biomass of plant and soil nematodes as well as environmental factors (climate, soil environment, and soil resource) at 44 field sites (220 plots) along a 2000‐km east–west transect and a 900‐km south–north transect across grasslands on the Mongolian Plateau. Regression was used to examine the relationships between diversity components and biomass of plants and nematodes. Hierarchical structural equation modelling ( SEM ) was performed to analyse the effects of environmental factors on diversity components and their linkages to biomass. Results The biomass of plants and nematodes correlated positively with biodiversity measures for plants and nematodes except that nematode biomass decreased as nematode β‐diversity increased. The relationship between plant and soil nematodes was positive for biomass and for α‐ and γ‐diversity, but it was negative for β‐diversity. When considering the environmental factors, hierarchical SEM indicated that variation in plant or nematode γ‐diversity was associated with changes in climate, soil environment, and soil resources. Variation in plant or nematode α‐diversity was mainly associated with changes in γ‐diversity, while variation in the plant or nematode β‐diversity was mainly associated with changes in γ‐diversity and climate. The climate and soil resources explained most of the variation in plant biomass, whereas climate and α‐ and γ‐diversity explained most of the variation in nematode biomass. Surprisingly, plant biomass or diversity was only weakly related to soil nematodes when considering the environmental factors. Main conclusions Diversity and biomass patterns of nematodes and perhaps of other below‐ground organisms are different from those of plants, and this difference is highly climate dependent. These findings suggest that a more complete understanding of diversity–biomass relationships will require further examination of more taxa across a broader range of environmental gradients.

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Adaptability of various models of the water production function for rice in Jilin Province, China - Weiguo Cheng; Wenxi Lu; Xin Xin; Zheng Zhang; Haibo Chu (Paddy and Water Environment, 2016)

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag - TsingHai Wang; Yan-Chen Lai; Chia-Che Chiang; Yu-Rong Cheng; Yi-Kong Hsieh; Chu-Fang Wang (Environmental Monitoring and Assessment, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Trabecular Bone Morphological Analysis for Preclinical Osteoporosis Application Using Micro Computed Tomography Scanner - David Shih-Chun Jin; Chien-Hao Chu; Jyh-Cheng Chen (Journal of Medical and Biological Engineering, 2016)

Fine mapping of a palea defective 1 (pd1), a locus associated with palea and stamen development in rice - Chunyan Xiang; Xinxing Liang; Ruizhen Chu; Min Duan; Jinping Cheng; Zhengquan Ding; Jianfei Wang (Plant Cell Reports, 2015)

Automatic Contrast Enhancement of Brain MR Images Using Hierarchical Correlation Histogram Analysis - Chiao-Min Chen; Chih-Cheng Chen; Ming-Chi Wu; Gwoboa Horng; Hsien-Chu Wu; Shih-Hua Hsueh; His-Yun Ho (Journal of Medical and Biological Engineering, 2015)

S-Wave Velocity Structure of the Taiwan Chelungpu Fault Drilling Project (TCDP) Site Using Microtremor Array Measurements - Cheng-Feng Wu; Huey-Chu Huang (Pure and Applied Geophysics, 2015)

Design and synthesis of 5-chloro-2-hydroxy-3-triazolylbenzoic acids as HIV integrase inhibitors - Jie Chen; Cheng-Fu Liu; Cheng-Wen Yang; Cheng-Chu Zeng; Wei Liu; Li-Ming Hu (Medicinal Chemistry Research, 2015)

A new design method for extracorporeal high-intensity focused ultrasound annular array - Gin-Shin Chen; Yu-Cheng Lin; Chu-Chiang Chen (Medical & Biological Engineering & Computing, 2015)

Time-domain solution for transient dynamic response of a large-diameter thin-walled pipe pile - Xuanming Ding; Hanlong Liu; Jian Chu; Ke Cheng (Earthquake Engineering and Engineering Vibration, 2015)

FACTS: Fully Automatic CT Segmentation of a Hip Joint - Chengwen Chu; Cheng Chen; Li Liu; Guoyan Zheng (Annals of Biomedical Engineering, 2015)

High seroprevalence of human herpesvirus type 8 infection in males with advanced lung carcinoma - Cheng-Chuan Su; Chun-Liang Lai; Shih-Ming Tsao; Ming-Nan Lin; Tang-Yuan Chu (Medical Microbiology and Immunology, 2015)

Positive selection drives neofunctionalization of the UbiA prenyltransferase gene family - Jiao Wang; Shanshan Chu; Ying Zhu; Hao Cheng; Deyue Yu (Plant Molecular Biology, 2015)

Effects of Ankle Eversion, Limb Laterality, and Ankle Stabilizers on Transient Postural Stability During Unipedal Standing - Wen-Xin Niu; Jie Yao; Zhao-Wei Chu; Cheng-Hua Jiang; Ming Zhang; Yu-Bo Fan (Journal of Medical and Biological Engineering, 2015)

Design and synthesis of N-hydroxytriazole-4-carboxamides as HIV integrase inhibitors - Yue-Xia Bai; Long-Ji Li; Xiao-Li Wang; Cheng-Chu Zeng; Li-Ming Hu (Medicinal Chemistry Research, 2015)

Isolation and characterization of microsatellite DNA loci from Sillago sihama - YU-SONG GUO; ZHONG-DUO WANG; CHENG-ZHONG YAN; YU-LAN ZHANG; JIN-NAN ZHENG; YUAN-MIN XU; TAO DU; CHU-WU LIU (Journal of Genetics, 2014)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

New Peak Shear Strength Criterion of Rock Joints Based on Quantified Surface Description - Cai-Chu Xia; Zhi-Cheng Tang; Wei-Min Xiao; Ying-Long Song (Rock Mechanics and Rock Engineering, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Applying Genetic Algorithm and Neural Network to the Conjunctive Use of Surface and Subsurface Water - Yu Wen Chen; Liang Cheng Chang; Chun Wei Huang; Hone Jay Chu (Water Resources Management, 2013)

Reply to: Comment on ‘neutron imaging reveals internal plant water dynamics’ - Jeffrey M. Warren; Hassina Bilheux; Chu-Lin Cheng; Edmund Perfect (Plant and Soil, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Arsenic contamination in the freshwater fish ponds of Pearl River Delta: bioaccumulation and health risk assessment - Zhang Cheng; Kun-Ci Chen; Kai-Bin Li; Xiang-Ping Nie; Sheng Chun Wu; Chris Kong-Chu Wong; Ming-Hung Wong (Environmental Science and Pollution Research, 2013)

Neutron imaging reveals internal plant water dynamics - Jeffrey M. Warren; Hassina Bilheux; Misun Kang; Sophie Voisin; Chu-Lin Cheng; Juske Horita; Edmund Perfect (Plant and Soil, 2013)

A new furolactone-type lignan from Lycium chinense - Xing-Nuo Li; Chu Chu; Sheng-Qiang Tong; Dong-Ping Cheng; Ji-Zhong Yan (Natural Product Research, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

Salinity and temperature tolerance of brown-marbled grouper Epinephelus fuscoguttatus - Sha-Yen Cheng; Chih-Sung Chen; Jiann-Chu Chen (Fish Physiology and Biochemistry, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Promising outcomes in glutaric aciduria type I patients detected by newborn screening - Chee-Seng Lee; Yin-Hsiu Chien; Shinn-Forng Peng; Pin-Wen Cheng; Lih-Maan Chang; Ai-Chu Huang; Wuh-Liang Hwu; Ni-Chung Lee (Metabolic Brain Disease, 2013)

Priming mass spectrometry-based sulfoglycomic mapping for identification of terminal sulfated lacdiNAc glycotope - Shin-Yi Yu; Lan-Yi Chang; Chu-Wen Cheng; Chi-Chi Chou; Michiko N. Fukuda; Kay-Hooi Khoo (Glycoconjugate Journal, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

The effects of a sudden salinity change on cortisol, glucose, lactate, and osmolality levels in grouper Epinephelus malabaricus - Wen-Ching Tsui; Jiann-Chu Chen; Sha-Yen Cheng (Fish Physiology and Biochemistry, 2012)

Electronegative low-density lipoprotein induces cardiomyocyte apoptosis indirectly through endothelial cell-released chemokines - An-Sheng Lee; Guei-Jane Wang; Hua-Chen Chan; Fang-Yu Chen; Chia-Ming Chang; Chao-Yuh Yang; Yuan-Teh Lee; Kuan-Cheng Chang; Chu-Huang Chen (Apoptosis, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China - Ru Cheng Wang; A-Peng Yu; Jun Chen; Lei Xie; Jian-Jun Lu; Jin-Chu Zhu (Mineralogy and Petrology, 2012)

Integration of Optimal Dynamic Control and Neural Network for Groundwater Quality Management - Liang-Cheng Chang; Hone-Jay Chu; Chin-Tsai Hsiao (Water Resources Management, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Polysaccharides purified from the submerged culture of Ganoderma formosanum stimulate macrophage activation and protect mice against Listeria monocytogenes infection - Cheng-Li Wang; Chia-Chen Pi; Chu-Wei Kuo; Yu-Jing Zhuang; Kay-Hooi Khoo; Wen-Hsiung Liu; Chun-Jen Chen (Biotechnology Letters, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Crystal structure of tarocystatin–papain complex: implications for the inhibition property of group-2 phytocystatins - Ming-Hung Chu; Kai-Lun Liu; Hsin-Yi Wu; Kai-Wun Yeh; Yi-Sheng Cheng (Planta, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Genomic aspects of research involving polyploid plants - Xiaohan Yang; Chu-Yu Ye; Zong-Ming Cheng; Timothy J. Tschaplinski; Stan D. Wullschleger; Weilun Yin; Xinli Xia; Gerald A. Tuskan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

ZEBRA2, encoding a carotenoid isomerase, is involved in photoprotection in rice - Chenglin Chai; Jun Fang; Yang Liu; Hongning Tong; Yanqing Gong; Yiqin Wang; Min Liu; Youping Wang; Qian Qian; Zhukuan Cheng; Chengcai Chu (Plant Molecular Biology, 2011)

Assaults against nurses of general and psychiatric hospitals in Taiwan - Judith Shu-Chu Shiao; Yuntin Tseng; Yueh-Tzu Hsieh; Jui-Yeh Hou; Yawen Cheng; Yueliang Leon Guo (International Archives of Occupational and Environmental Health, 2010)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Role of Diverse Non-Systemic Fungal Endophytes in Plant Performance and Response to Stress: Progress and Approaches - Zhi-lin Yuan; Chu-long Zhang; Fu-cheng Lin (Journal of Plant Growth Regulation, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Synoptic weather typing and typhoon with an application to Chiayi, Taiwan: potential for future climate change impact analysis - Chad Shouquan Cheng; Pao-Shan Yu; Qian Li; Guilong Li; Jung-Lien Chu (Paddy and Water Environment, 2009)

Modeling waterbird diversity in irrigation ponds of Taoyuan, Taiwan using an artificial neural network approach - Wei-Ta Fang; Hone-Jay Chu; Bai-You Cheng (Paddy and Water Environment, 2009)

Adsorption of lambda-cyhalothrin and cypermethrin on two typical Chinese soils as affected by copper - Jun Liu; Xiaomeng Lü; Jimin Xie; Yafei Chu; Cheng Sun; Qian Wang (Environmental Science and Pollution Research, 2009)

Apparent formation factor for leachate-saturated waste and sediments: Examples from the USA and China - Philip J. Carpenter; Aizhong Ding; Lirong Cheng; Puxin Liu; Fulu Chu (Journal of Earth Science, 2009)

Exopolysaccharide production of Lactobacillus salivarius BCRC 14759 and Bifidobacterium bifidum BCRC 14615 - Chu-Ting Liu; I-Ting Hsu; Cheng-Chun Chou; Pei-Ren Lo; Roch-Chui Yu (World Journal of Microbiology and Biotechnology, 2009)

ZAK induces MMP-2 activity via JNK/p38 signals and reduces MMP-9 activity by increasing TIMP-1/2 expression in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Wei-Wen Kuo; Hsi-Chin Wu; Tung-Yuan Lai; Chun-Hsien Wu; Jin-Ming Hwang; Wen-Hong Wang; Fuu-Jen Tsai; Jaw-Ji Yang; Chih-Yang Huang; Chun-Hsien Chu (Molecular and Cellular Biochemistry, 2009)

Application of Optimal Control and Fuzzy Theory for Dynamic Groundwater Remediation Design - Hone-Jay Chu; Liang-Cheng Chang (Water Resources Management, 2009)

Chest wall abscess due to Prevotella bivia - Gwo-jong Hsu; Cheng-ren Chen; Mei-chu Lai; Shi-ping Luh (Journal of Zhejiang University-SCIENCE B, 2009)

Simultaneously monitoring the particle size distribution, morphology and suspended solids concentration in wastewater applying digital image analysis (DIA) - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Peginterferon vs. interferon in the treatment of different HCV genotype infections in HIV patients - S. Zhao; D. Cheng; E. Liu; H. Yu; H. Yang; X. Xue; Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Dry deposition study by using dry deposition plate and water surface sampler in Shalu, central Taiwan - Chia-Chun Chu; Guor-Cheng Fang; Jhy-Cherng Chen; I-Lin Yang (Environmental Monitoring and Assessment, 2008)

Balance between facilitation and resource competition determines biomass–density relationships in plant populations - Cheng‐Jin Chu; Fernando T. Maestre; Sa Xiao; Jacob Weiner; You‐Shi Wang; Zheng‐Hu Duan; Gang Wang (Ecology Letters, 2008)
Theories based on competition for resources predict a monotonic negative relationship between population density and individual biomass in plant populations. They do not consider the role of facilitative interactions, which are known to be important in high stress environments. Using an individual‐based ‘zone‐of‐influence’ model, we investigated the hypothesis that the balance between facilitative and competitive interactions determines biomass–density relationships. We tested model predictions with a field experiment on the clonal grass Elymus nutans in an alpine meadow. In the model, the relationship between mean individual biomass and density shifted from monotonic to humped as abiotic stress increased. The model results were supported by the field experiment, in which the greatest individual and population biomass were found at intermediate densities in a high‐stress alpine habitat. Our results show that facilitation can affect biomass–density relationships.

Combined effect of cypermethrin and copper on catalase activity in soil - Jun Liu; Jimin Xie; Yafei Chu; Cheng Sun; Chuanxiang Chen; Qian Wang (Journal of Soils and Sediments, 2008)

Seasonal change and correlation with environmental parameters for 2-MIB in Feng-Shen Reservoir, Taiwan - Shu-Chu Tung; Tsair-Fuh Lin; Feng-Cheng Yang; Chia-Lin Liu (Environmental Monitoring and Assessment, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Lipopolysaccharide induces cellular hypertrophy through calcineurin/NFAT-3 signaling pathway in H9c2 myocardiac cells - Chung-Jung Liu; Yi-Chang Cheng; Kung-Wei Lee; Hsi-Hsien Hsu; Chun-Hsien Chu; Fuu-Jen Tsai; Chang-Hai Tsai; Chia-Yih Chu; Jer-Yuh Liu; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2008)

Differentiation of two powdery mildews of sunflower (Helianthus annuus) by a PCR-mediated method based on ITS sequences - Ruey-Shyang Chen; Chishih Chu; Chi-Wei Cheng; Wen-Yu Chen; Jwu-Guh Tsay (European Journal of Plant Pathology, 2008)

Chromosomal polymorphism of ribosomal genes in the genus Oryza - Mei-Chu Chung; Yung-I Lee; Yueh-Yun Cheng; Yi-Jia Chou; Chia-Fu Lu (Theoretical and Applied Genetics, 2008)

South China Sea wave characteristics during typhoon Muifa passage in winter 2004 - Peter C. Chu; Kuo-Feng Cheng (Journal of Oceanography, 2008)

Nitricoxide synthase-induced oxidative stress in prolonged alcoholic myopathies of rats - Jianfeng Wang; Haiying Chu; Hua Zhao; Xueying Cheng; Yanli Liu; Wei Jin; Jinyao Zhao; Bo Liu; Yanfang Ding; Haiying Ma (Molecular and Cellular Biochemistry, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Measurements of Wastewater True Color by 4/6 Wavelength Methods and Artificial Neural Network - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2006)

An integrated map of Oryza sativa L. chromosome 5 - Fang-I Kao; Yueh-Yun Cheng; Teh-Yuan Chow; Hong-Hwa Chen; Shu-Mei Liu; Chia-Hsiung Cheng; Mei-Chu Chung (Theoretical and Applied Genetics, 2006)

Integration of transfer function model and back propagation neural network for forecasting storm sewer flow in Taipei metropolis - Chih-Chiang Lu; Chu-Hui Chen; Tian-Chyi J. Yeh; Cheng-Mau Wu; I-Fang Yau (Stochastic Environmental Research and Risk Assessment, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

MULTIPLE INITIAL CULTURE CONDITIONS ENHANCE THE ESTABLISHMENT OF CELL LINES FROM PRIMARY OVARIAN CANCER SPECIMENS - CARA C. BERTOZZI; CHENG-YI CHANG; SONYA JAIRAJ; XIAOCHUAN SHAN; JIA HUANG; BARBARA L. WEBER; CHRISTINA S. CHU; RICHARD G. CARROLL (In Vitro Cellular & Developmental Biology - Animal, 2006)

Multiple Initial Culture Conditions Enhance the Establishment of Cell Lines from Primary Ovarian Cancer Specimens - Cara C. Bertozzi; Cheng-Yi Chang; Sonya Jairaj; Xiaochuan Shan; Jia Huang; Babara L. Weber; Christina S. Chu; Richard G. Carroll (In Vitro Cellular & Developmental Biology - Animal, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

A homozygous COL6A2 intron mutation causes in-frame triple-helical deletion and nonsense-mediated mRNA decay in a patient with Ullrich congenital muscular dystrophy - Laura Lucarini; Betti Giusti; Rui-Zhu Zhang; Te-Cheng Pan; Cecilia Jimenez-Mallebrera; Eugenio Mercuri; Francesco Muntoni; Guglielmina Pepe; Mon-Li Chu (Human Genetics, 2005)

The relationship between HPV16 and expression of CD44v6, nm23H1 in esophageal squamous cell carcinoma - W.-K. Liu; Y.-L. Chu; F. Zhang; P. Chen; F. Cheng; H. Wang; Y.-Y. Jia; T.-Y. Ma (Archives of Virology, 2005)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Dissection of cry Gene Profiles of Bacillus thuringiensis Isolates in Taiwan - Fu-Chu Chen; Ming-Chu Tsai; Cheng-Hung Peng; Kin-Fu Chak (Current Microbiology, 2004)

Predicting Scalar Source-Sink and Flux Distributions Within a Forest Canopy Using a 2-D Lagrangian Stochastic Dispersion Model - Cheng-I Hsieh; Mario Siqueira; Gabriel Katul; Chia-Ren Chu (Boundary-Layer Meteorology, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

In vitro and in vivo transfection and expression of plasmid-based non-viral vector for erythropoietin gene therapy - Xianmin Zhu; Zhongmei Chu; Yunlong Hu; Jianfeng Lu; Cheng Liu; Xianming Qu; Yi Zhang (Biotechnology Letters, 2002)

The characteristics and main problems of minority regions in China - Luo-cheng Zhang; Chu-cai Wu (Chinese Geographical Science, 2001)

Comparison between `in vivo' and `in vitro' methods for evaluating tumor angiogenesis using cervical carcinoma as a model - Wen-Fang Cheng; Chien-Nan Lee; Chi-An Chen; Jan-Show Chu; Cheng-Che S. Kung; Chang-Yao Hsieh; Fon-Jou Hsieh (Angiogenesis, 1999)